Steel plates, components and their manufacturing methods

By adjusting the composition and microstructure of the steel plate base material, the problem of poor plasticity and impact damage performance while improving impact resistance and energy absorption capacity of existing steel plates is solved, and high-strength and good deformation steel plates are achieved, suitable for automotive impact energy absorption member parts.

JP7666640B2Active Publication Date: 2025-04-22JFE STEEL CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023565463
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-11
Filing Date
2023-02-27
Publication Date
2025-04-22
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

While improving impact resistance and energy absorption, existing steel plates are difficult to maintain good plasticity and impact damage performance, making it difficult to meet the needs of high strength and high deformation in practical applications.

Method used

By adjusting the substrate composition and microstructure of the steel plate, ensure that the manganese content in the substrate is between 2.00% and 3.50%, retain a certain proportion of the remnant austenite and new martensite, and control the carbon content between 0.050% and 0.400% to form an optimized steel structure.

Benefits of technology

It achieves high strength (TS ≥ 1180 MPa), high impact resistance, good plasticity and impact damage performance of steel plates, and is suitable for impact energy absorption members of automobiles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666640000015
    Figure 0007666640000015
  • Figure 0007666640000016
    Figure 0007666640000016
  • Figure 0007666640000017
    Figure 0007666640000017
Patent Text Reader

Abstract

Provided are: a steel sheet that has a high YS and a TS of at least 1180 MPa, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance characteristics (bending fracture characteristics and axial crushing characteristics) when being crushed; a member; and methods for producing the steel sheet and the member. According to the present invention, a base steel sheet has a predetermined component composition. In the steel structure of the base steel sheet: bainitic ferrite, tempered martensite, residual austenite, and fresh martensite are contained in predetermined ranges; the concentration of carbon in the residual austenite and the density of carbides in the tempered martensite are in predetermined ranges; the amount of diffusible hydrogen is at most 0.50 ppm by mass; and, when a V-VDA bending test is conducted up to the maximum load point, the length of a crack in an L cross-section is at most 400 μm, and the amount of change between before and after processing in the particle size of bainitic ferrite in the thickness direction in a predetermined region of VDA bending is at most 5.0.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel plate, a member made of the steel plate, and a method for producing the same. [Background technology]

[0002] In recent years, from the viewpoint of protecting the global environment, improving the fuel efficiency of automobiles has become an important issue. For this reason, there has been a growing movement to reduce the weight of automobile bodies by increasing the strength and reducing the thickness of steel sheets, which are the raw materials for automobile parts.

[0003] In addition, social demands for improved collision safety of automobiles are becoming stronger, and therefore there is a demand for the development of steel sheets that not only have high strength but also have excellent impact resistance properties when an automobile collides while traveling (hereinafter simply referred to as impact resistance properties).

[0004] As an example of a steel sheet that can be used as a raw material for such automobile components, Patent Document 1 discloses a high-strength steel sheet that has a component composition that contains, expressed by mass%, 0.04 to 0.22% C, 1.0% or less Si, 3.0% or less Mn, 0.05% or less P, 0.01% or less S, 0.01 to 0.1% Al, and 0.001 to 0.005% N, with the balance being Fe and unavoidable impurities, and that is composed of a ferrite phase as a main phase and a martensite phase as a second phase, and that has a maximum grain size of 2 μm or less and an area ratio of the martensite phase of 5% or more, and has excellent stretch flangeability and crash resistance.

[0005] In addition, Patent Document 2 discloses a method for forming a 0.2 g / m2 Ni alloy on a cold-rolled steel sheet from which a surface layer of 0.1 μm or more has been removed by grinding. 2 More than 2.0g / m 2The following hot-dip galvanized steel sheet has a hot-dip galvanized layer on the surface of a pre-galvanized cold rolled steel sheet, and contains, by mass%, C: 0.05% or more and 0.4% or less, Si: 0.01% or more and 3.0% or less, Mn: 0.1% or more and 3.0% or less, P: 0.04% or less, S: 0.05% or less, N: 0.01% or less, Al: 0.01% or more and 2.0% or less, Si + Al > 0.5%, the balance being Fe and unavoidable impurities, and the microstructure contains, by volume fraction, 40% or more of ferrite as a main phase, 8% or more of retained austenite, two or more of three types of martensite [1] [2] [3] specified below including martensite [3], 1% or more of bainite, and 0 to 10% of pearlite, and further contains the three types of martensite [1] [2] [3] as specified below. A high-strength hot-dip galvanized steel sheet having excellent coating adhesion and formability, characterized in that the steel sheet has a surface in which the sites [1], [2] and [3] are, in volume fraction, martensite [1]: 0% or more and 50% or less, martensite [2]: 0% or more and less than 20%, and martensite [3]: 1% or more and 30% or less, respectively, and has a hot-dip galvanized layer containing less than 7% Fe and the balance consisting of Zn, Al and unavoidable impurities, and has a tensile strength TS (MPa), total elongation EL (%) and hole expansion ratio λ (%) of TS×EL of 18000 MPa·% or more and TS×λ of 35000 MPa·% or more, and a tensile strength of 980 MPa or more (martensite [1]: C concentration (CM1) is less than 0.8%, and hardness Hv1 is Hv1 / (-982.1×CM1 2 +1676×CM1+189)≦0.60, martensite [2]: C concentration (CM2) is 0.8% or more, and hardness Hv2 is Hv2 / (-982.1×CM2 2 +1676×CM2+189)≦0.60, martensite [3]: C concentration (CM3) is 0.8% or more, and hardness Hv3 is Hv3 / (-982.1×CM3 2 +1676×CM3+189)≧0.80 is disclosed.

[0006] Patent Document 3 discloses a high-strength hot-dip galvanized steel sheet having a component composition, in mass%, of C: 0.15% or more and 0.25% or less, Si: 0.50% or more and 2.5% or less, Mn: 2.3% or more and 4.0% or less, P: 0.100% or less, S: 0.02% or less, Al: 0.01% or more and 2.5% or less, with the balance being Fe and unavoidable impurities, and having, in area ratios, a tempered martensite phase: 30% or more and 73% or less, a ferrite phase: 25% or more and 68% or less, a retained austenite phase: 2% or more and 20% or less, and other phases: 10% or less (including 0%), and the other phases include a martensite phase: 3% or less (including 0%) and a bainitic ferrite phase: less than 5% (including 0%), the tempered martensite phase has an average crystal grain size of 8 μm or less, and the retained austenite phase has a C content of less than 0.7% by mass. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 3887235 [Patent Document 2] Patent No. 5953693 [Patent Document 3] Patent No. 6052472 Summary of the Invention [Problem to be solved by the invention]

[0008] Incidentally, currently, the application of impact energy absorbing members of automobiles, such as front side members and rear side members, is limited to steel sheets with a tensile strength (hereinafter also referred to as TS) of 590 MPa class.

[0009] That is, in order to increase the absorbed energy during impact (hereinafter also referred to as impact absorption energy), it is effective to improve the yield stress (hereinafter also referred to as YS). However, when the TS and YS of a steel sheet are increased, generally, the press formability, particularly properties such as ductility, hole expandability, and bendability, decrease. Therefore, when it is assumed that such a steel sheet with increased TS and YS is applied to the above-mentioned impact energy absorbing member of an automobile, not only does press forming become difficult, but the member is cracked in an axial crushing test simulating a crash test, in other words, the actual impact absorption energy is not as high as expected from the YS value. Therefore, the current situation is that the above-mentioned impact energy absorbing member is limited to the application of a steel sheet with a TS of 590 MPa class.

[0010] In fact, the steel sheets disclosed in Patent Documents 1 to 3 have a TS of 1180 MPa or more, and cannot be said to have a high YS, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during crushing (flexural fracture properties and axial crushing properties).

[0011] The present invention has been developed in view of the above-mentioned current situation, and aims to provide a steel plate having a tensile strength TS of 1180 MPa or more, high yield stress YS, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during crushing (flexural fracture properties and axial crushing properties), together with an advantageous manufacturing method thereof. Another object of the present invention is to provide a member made of the above-mentioned steel plate and a method for manufacturing the same.

[0012] The steel sheet referred to here includes a zinc-plated steel sheet, and the zinc-plated steel sheet is a hot-dip galvanized steel sheet (hereinafter also referred to as GI) or an alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA).

[0013] Here, the tensile strength TS is measured by a tensile test in accordance with JIS Z 2241 (2011). In addition, having a high yield stress YS, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during crushing (bending fracture properties and axial crushing properties) means satisfying the following. A high yield stress YS means that the YS measured in a tensile test conforming to JIS Z 2241 (2011) satisfies the following formula (A) or (B) depending on the TS measured in the tensile test. (A) When 1180MPa≦TS<1320MPa, 750MPa≦YS (B) When TS is 1320MPa or less, YS is 850MPa or less

[0014] In addition, excellent ductility means that the total elongation (El) measured in a tensile test conforming to JIS Z 2241 (2011) satisfies the following formula (A) or (B) depending on the TS measured in the tensile test. (A) When 1180MPa≦TS<1320MPa, 12.0%≦El (B) When TS is 1320MPa or less, 10.0% or less El

[0015] In addition, excellent hole expansion property means that the limit hole expansion ratio (λ) measured in a hole expansion test conforming to JIS Z 2256 (2020) is 30% or more.

[0016] In addition, excellent bendability refers to a bending angle (α) of 80° or more at maximum load measured in a bending test conforming to the VDA standard (VDA238-100) prescribed by the German Association of the Automotive Industry.

[0017] In addition, excellent bending fracture properties are defined as the stroke (S Fmax ) is 26.0 mm or more.

[0018] In addition, excellent axial crushing properties means that after an axial crushing test, there are three or less fractures (visual cracks) within an area of ​​R = 5.0 mm, 200 mm at the two lower bend ridges in Figure 6-1(b) (see area Cx in Figure 6-1).

[0019] The above El, λ, and α are characteristics that indicate the ease of forming steel sheets during press forming. On the other hand, the V-VDA bending test is a test that simulates the deformation and fracture behavior of the bending ridge in a crash test, and the stroke (S Fmax ) is a characteristic that indicates the resistance of a component to cracking. [Means for solving the problem]

[0020] The present inventors have conducted extensive research in order to achieve the above object. As a result, the composition of the base steel sheet of the steel sheet is appropriately adjusted, and the steel structure of the base steel sheet of the steel sheet has an area ratio of bainitic ferrite: 3.0% or more and 20.0% or less, an area ratio of tempered martensite (excluding retained austenite): 40.0% or more and 90.0% or less, an area ratio of retained austenite: more than 3.0% and 15.0% or less, a carbon concentration in the retained austenite: 0.60 mass% or more and 1.30 mass% or less, an area ratio of fresh martensite: 10.0% or less (including 0.0%), and a density of carbides in the tempered martensite of 8.0 particles / μm 2 It has been found that a steel sheet having a tensile strength TS of 1180 MPa or more, high YS, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during crushing (bending fracture properties and axial crushing properties) can be obtained by having a steel structure as described below, the amount of diffusible hydrogen in the base steel sheet being 0.50 ppm by mass or less, and further, performing a V-VDA bending test up to the maximum load point, the length of the crack is 400 μm or less in the L cross section at the overlapping region of the V-bend ridge line and the VDA bend ridge line, and further, in a region formed at a position 50 μm on each side of the start line, which exists from the outer bend apex of the VDA bend as the starting point in the sheet thickness direction, the ratio of the average grain size before processing to the average grain size after processing (change before and after processing: average grain size before processing (nm) / average grain size after processing (nm)) is 5.0 or less. The present invention has been completed based on the above findings and through further investigation.

[0021] That is, the gist and configuration of the present invention are as follows. [1] A steel plate having a base steel plate, the base steel plate comprising: In mass%, C: 0.050% or more and 0.400% or less, Si: more than 0.75% and less than 3.00%, Mn: 2.00% or more and less than 3.50% P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% to 2.000% and N: 0.0100% or less The remainder of the composition is Fe and unavoidable impurities. The base steel sheet is Area ratio of bainitic ferrite: 3.0% to 20.0% Area ratio of tempered martensite: 40.0% to 90.0% Area ratio of retained austenite: more than 3.0% and less than 15.0% Carbon concentration in retained austenite: 0.60 mass% or more and 1.30 mass% or less, Area ratio of fresh martensite: 10.0% or less, Density of carbides in tempered martensite: 8.0 particles / μm 2 below, and The base steel sheet has a diffusible hydrogen content of 0.50 ppm by mass or less, In addition, a V-VDA bending test was performed up to the maximum load point. At L section, The crack length is 400 μm or less, Furthermore, in the region formed at a position up to 50 μm on each side of the start line in the vertical direction from the start point of the bend apex on the outer side of the VDA bend to a position of 50 μm in the plate thickness direction, Regarding the average grain size of bainitic ferrite in the sheet thickness direction, the ratio of the average grain size before processing to the average grain size after processing is 5.0 or less; A steel plate having a tensile strength of 1180MPa or more. [2] The composition of the base steel sheet further comprises, in mass%, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co:0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM: 0.0200% or less The steel sheet according to the above [1], comprising at least one selected from the following: [3] The steel sheet according to [1] or [2] above, which has a zinc-plated layer as the outermost layer on one or both sides of the steel sheet. [4] When the base steel sheet has a surface layer of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, The surface layer has a soft surface layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 points or more in a 50 μm × 50 μm region of the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, The ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nanohardness of the sheet surface at a position of 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, The steel sheet according to any one of the above [1] to [3], wherein the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less. [5] The steel sheet according to any one of [1] to [4] above, which has a metal plating layer formed on the base steel sheet on one or both sides of the steel sheet. [6] A member made using the steel plate according to any one of [1] to [5] above. [7] A hot rolling process in which a steel slab having the composition described in [1] or [2] is hot rolled to obtain a hot rolled steel sheet; A pickling process for pickling the hot-rolled steel sheet; An annealing process in which the steel sheet after the pickling process is annealed at an annealing temperature of (Ac1+0.4×(Ac3−Ac1))° C. or more and 900° C. or less for an annealing time of 20 seconds or more; A first cooling step of cooling the steel sheet after the annealing step to a first cooling stop temperature of 400°C or more and 600°C or less; The steel sheet after the first cooling step is cooled to a second cooling stop temperature of 100°C or more and 300°C or less at an average cooling rate of 25.0°C / sec or less, During the cooling process, the steel plate is subjected to a load of 2.0 kgf / mm in the temperature range of 300°C to 450°C. 2 Apply the above tension at least once, after that, A treatment in which the steel sheet is subjected to four or more passes while being in contact with a roll having a diameter of 500 mm or more and 1500 mm or less for one pass for 1 / 4 of the circumference of the roll; and A second cooling process in which the steel sheet is subjected to two or more passes while being brought into contact with a roll having a diameter of 500 mm or more and 1500 mm or less for 1 / 2 rotation of the roll per pass; a reheating process in which the steel sheet after the second cooling process is heated to a tempering temperature in a temperature range of more than 300° C. and not more than 500° C., and is held in the temperature range for a tempering time of 20 seconds or more and 900 seconds or less, and during the reheating process, a carbide control parameter CP represented by the following formula (1) is set to 10,000 or more and 15,000 or less, Or even The method for producing a steel sheet includes a cold rolling step of cold rolling the steel sheet after the pickling step and before the annealing step to obtain a cold-rolled steel sheet. CP=(T+273)×(k+1.2×logt)...Equation (1) where T is the tempering temperature (°C), k is a material constant dependent on the C content, and t is the tempering time (sec). k = -6 × C M +17.8, C M is the carbon content (mass%) in the martensite formed in the second cooling step. [8] The method for producing a steel sheet according to [7], further comprising a galvanizing step of subjecting the steel sheet after the first cooling step and before the second cooling step to a galvanizing treatment to form a galvanized layer on the steel sheet. [9] The method for producing a steel sheet according to [7] or [8] above, wherein the annealing in the annealing step is carried out in an atmosphere with a dew point of -30°C or higher.

[10] The method for producing a steel sheet according to any one of [7] to [9] above, further comprising a metal plating step of applying metal plating to one or both sides of the steel sheet to form a metal plating layer after the pickling step and before the annealing step.

[11] A method for producing a component, comprising the step of subjecting the steel plate according to any one of [1] to [5] above to at least one of forming and joining to produce a component. Effect of the Invention

[0022] According to the present invention, a steel plate having a tensile strength TS of 1180 MPa or more, high yield stress YS, excellent press formability (ductility, hole expandability and bendability), and fracture resistance properties during crushing (bending fracture properties and axial crushing properties) can be obtained. Furthermore, members made from the steel plate of the present invention have high strength and excellent impact resistance, and can therefore be used extremely advantageously in impact energy absorbing members for automobiles. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 shows SEM tissue images to explain the identification of the tissue. [Figure 2-1] Fig. 2-1(a) is a diagram for explaining V-bending (primary bending) in the V-VDA bending test of the embodiment. Fig. 2-1(b) is a diagram for explaining VDA bending (secondary bending) in the V-VDA bending test of the embodiment. [Figure 2-2] Fig. 2-2(c) is a perspective view showing a test piece subjected to V-bending (primary bending) in V-VDA. Fig. 2-2(d) is a perspective view showing a test piece subjected to VDA bending (secondary bending) in V-VDA. [Figure 2-3] Figure 2-3(e) is a perspective view of a test piece subjected to VDA bending (secondary bending) in V-VDA and an L-section observation surface. Figure 2-3(f) is a cross-sectional view showing the measurement points of the change in the grain size of bainitic ferrite in the plate thickness direction before and after processing in the L-section observation surface of a test piece subjected to VDA bending (secondary bending) in V-VDA. [Figure 2-4] FIG. 2-4 is a schematic diagram for explaining the AB region. [Diagram 3] FIG. 3 is a schematic diagram of the stroke-load curve obtained when the V-VDA test was performed. [Figure 4] FIG. 4 is a structural image taken by SEM to explain the crack length measurement specified in the present invention (Example No. 36 of the present invention). [Diagram 5]Fig. 5(a) is a structural image taken by SEM to explain a method for measuring the grain size of bainitic ferrite before deformation by processing specified in the present invention (Example No. 35 of the present invention in the examples). Fig. 5(b) is a structural image taken by SEM to explain a method for measuring the grain size of bainitic ferrite after deformation by processing specified in the present invention (Example No. 35 of the present invention in the examples). [Figure 6-1] Fig. 6-1(a) is a front view of a test member manufactured for the axial crush test of the embodiment, in which a hat-shaped member and a steel plate are spot-welded together. Fig. 6-1(b) is a perspective view of the test member shown in Fig. 6-1(a). [Figure 6-2] FIG. 6-2(c) is a schematic diagram for explaining the axial crush test of the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention will be described based on the following embodiments.

[0025] [1. Steel plate] The steel sheet of the present invention is a steel sheet having a base steel sheet, and the base steel sheet contains, by mass%, C: 0.050% or more and 0.400% or less, Si: more than 0.75% and 3.00% or less, Mn: 2.00% or more and less than 3.50%, P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% or more and 2.000% or less, and N: 0.0100% or less, with the balance being Fe and unavoidable impurities. The steel sheet has a composition in which the area ratio of bainitic ferrite is 3.0% or more and 20.0% or less, the area ratio of tempered martensite is 40.0% or more and 90.0% or less, the area ratio of retained austenite is more than 3.0% and 15.0% or less, the carbon concentration in the retained austenite is 0.60 mass% or more and 1.30 mass% or less, the area ratio of fresh martensite is 10.0% or less, and the density of carbides in the tempered martensite is 8.0 pieces / μm 2or less, the amount of diffusible hydrogen in the base steel sheet is 0.50 mass ppm or less, and further, when a V-VDA bending test is performed up to the maximum load point, the length of the crack in the L cross section is 400 μm or less, and further, in a region formed at a position from each position of a start line that exists from the outer bend apex of the VDA bend to a position 50 μm in the sheet thickness direction to a position 50 μm on each side of the start line in the perpendicular direction, with regard to the average grain size of bainitic ferrite in the sheet thickness direction, the ratio of the average grain size before processing to the average grain size after processing is 5.0 or less, and the tensile strength is 1180 MPa or more. The steel sheet may have a zinc plating layer as the outermost layer on one or both sides of the steel sheet. The steel sheet having a zinc plating layer may be a zinc-plated steel sheet.

[0026] Ingredient composition First, the composition of the base steel sheet of the steel sheet according to the embodiment of the present invention will be described. Note that the unit of the composition is always "mass %", but hereinafter, unless otherwise specified, it will be simply shown as "%".

[0027] C: 0.050% or more and 0.400% or less C is an effective element for generating appropriate amounts of fresh martensite, tempered martensite, bainitic ferrite, and retained austenite to ensure a tensile strength TS of 1180 MPa or more and a high YS. If the C content is less than 0.050%, the area ratio of ferrite increases, making it difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. On the other hand, when the C content exceeds 0.400%, the carbon concentration in the retained austenite increases excessively, and as a result, the hardness of the fresh martensite formed by the deformation-induced transformation when the steel plate is subjected to punching in the hole expansion test or V-bending in the V-VDA test increases significantly, promoting the subsequent formation of voids and crack propagation, and decreasing the desired λ and S. Fmax cannot be achieved. Therefore, the C content is set to 0.050% or more and 0.400% or less. The C content is preferably 0.100% or more. Moreover, the C content is preferably 0.300% or less.

[0028] Si: more than 0.75% and less than 3.00% Silicon inhibits the formation of carbides during cooling after annealing and promotes the formation of retained austenite. In other words, silicon is an element that affects the volume fraction of retained austenite and the carbon concentration in the retained austenite. If the silicon content is 0.75% or less, the volume fraction of retained austenite decreases, and ductility decreases. On the other hand, if the Si content exceeds 3.00%, the area ratio of ferrite increases excessively, making it difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. In addition, the carbon concentration in the austenite during annealing increases excessively, making it difficult to obtain the desired λ and S. Fmax cannot be achieved. Therefore, the Si content is set to more than 0.75% and not more than 3.00%, and is preferably set to not more than 2.00%.

[0029] Mn: 2.00% or more and less than 3.50% Mn is an element that adjusts the area ratio of bainitic ferrite, tempered martensite, etc. Here, if the Mn content is less than 2.00%, the area ratio of ferrite increases excessively, making it difficult to achieve a TS of 1180 MPa or more. In addition, this also leads to a decrease in YS. On the other hand, when the Mn content is 3.50% or more, the martensite transformation start temperature Ms (hereinafter also referred to simply as the Ms point or Ms) decreases, and the martensite generated in the second cooling step decreases. As a result, the martensite generated during the final cooling step increases, and the martensite generated at that time is not sufficiently tempered, and the area ratio of hard fresh martensite increases. Fresh martensite becomes the starting point of void generation during the hole expansion test, VDA bending test, or V-VDA bending test, and when the area ratio of fresh martensite exceeds 10%, the desired λ, α, and S are not obtained. Fmax cannot be achieved. Therefore, the Mn content is set to 2.00% or more and less than 3.50%. The Mn content is preferably 2.50% or more. Moreover, the Mn content is preferably 3.20% or less.

[0030] P: 0.001% or more and 0.100% or less P is an element that has a solid solution strengthening effect and increases the TS and YS of steel sheets. To obtain this effect, the P content is set to 0.001% or more. On the other hand, if the P content exceeds 0.100%, P segregates to the prior austenite grain boundaries and embrittles the grain boundaries. Therefore, after the steel sheet is punched or V-bended in the V-VDA bending test, the amount of voids generated increases, and the desired λ and S are not obtained. Fmax cannot be achieved. Therefore, the P content is set to 0.001% or more and 0.100% or less, and preferably 0.030% or less.

[0031] S: 0.0001% or more and 0.0200% or less S exists as sulfide in steel. In particular, if the S content exceeds 0.0200%, the amount of voids generated increases after the steel sheet is punched or V-bended in the V-VDA bending test, and the desired λ and S Fmax cannot be achieved. Therefore, the S content is set to 0.0200% or less. The S content is preferably set to 0.0080% or less. However, due to restrictions on production technology, the lower limit of the S content is set to 0.0001% or more.

[0032] Al: 0.010% or more and 2.000% or less Al suppresses the formation of carbides during cooling after annealing and promotes the formation of retained austenite. In other words, Al is an element that affects the volume fraction of retained austenite and the carbon concentration in the retained austenite. To obtain these effects, the Al content is set to 0.010% or more. On the other hand, if the Al content exceeds 2.000%, the area ratio of ferrite increases excessively, making it difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. In addition, the C concentration in the austenite during annealing increases excessively, making it difficult to obtain the desired λ and S. Fmax cannot be achieved. Therefore, the Al content is set to 0.010% or more and 2.000% or less. The Al content is preferably 0.015% or more. Moreover, the Al content is preferably 1.000% or less.

[0033] N: 0.0100% or less N exists as nitrides in steel. In particular, if the N content exceeds 0.0100%, the amount of voids generated increases after the steel sheet is punched or V-bended in the V-VDA bending test, and the desired λ and S are not obtained. Fmax cannot be achieved. Therefore, the N content is set to 0.0100% or less. The N content is preferably set to 0.0050% or less. Although there is no particular lower limit for the N content, due to constraints on production technology, the N content is preferably 0.0005% or more.

[0034] The basic composition of the base steel sheet of the steel sheet according to one embodiment of the present invention has been described above, but the base steel sheet of the steel sheet according to one embodiment of the present invention has a composition containing the above basic components with the balance other than the above basic components including Fe (iron) and unavoidable impurities. Here, it is preferable that the base steel sheet of the steel sheet according to one embodiment of the present invention has a composition containing the above basic components with the balance consisting of Fe and unavoidable impurities.

[0035] In addition to the basic components described above, the base steel sheet of the steel sheet according to one embodiment of the present invention may contain at least one selected from the optional components shown below. The effects of the present invention can be obtained so long as the optional components shown below are contained in amounts not exceeding the upper limit amounts shown below, so no lower limit is set. When the optional elements shown below are contained in amounts less than the preferred lower limit values ​​described below, the elements are considered to be included as unavoidable impurities.

[0036] Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0. 200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200 %, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, and at least one selected from REM: 0.0200% or less.

[0037] Nb: 0.200% or less Nb increases TS and YS by forming fine carbides, nitrides or carbonitrides during hot rolling or annealing. To obtain such an effect, the Nb content is preferably 0.001% or more. The Nb content is more preferably 0.005% or more. On the other hand, if the Nb content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the coarse precipitates and inclusions may become the starting points of cracks during a hole expansion test, a VDA bending test or a V-VDA bending test, and the desired λ, α and S may not be obtained. Fmax Therefore, when Nb is contained, the Nb content is preferably 0.200% or less, and more preferably 0.060% or less.

[0038] Ti: 0.200% or less Like Nb, Ti increases TS and YS by forming fine carbides, nitrides, or carbonitrides during hot rolling or annealing. To obtain such an effect, the Ti content is preferably 0.001% or more. The Ti content is more preferably 0.005% or more. On the other hand, if the Ti content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the coarse precipitates and inclusions may become the starting points of cracks during a hole expansion test, a VDA bend test, or a V-VDA bend test, and the desired λ, α, and S may not be obtained. Fmax Therefore, when Ti is contained, the Ti content is preferably 0.200% or less, and more preferably 0.060% or less.

[0039] V:0.200% or less Like Nb and Ti, V increases TS and YS by forming fine carbides, nitrides, or carbonitrides during hot rolling or annealing. To obtain such an effect, the V content is preferably 0.001% or more. The V content is more preferably 0.005% or more. The V content is further preferably 0.010% or more, and even more preferably 0.030% or more. On the other hand, if the V content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the coarse precipitates and inclusions may become the starting points of cracks during a hole expansion test, a VDA bending test, or a V-VDA bending test, and the desired λ, α, and S may not be obtained. Fmax Therefore, when V is contained, the V content is preferably 0.200% or less, and more preferably 0.060% or less.

[0040] B: 0.0100% or less B is an element that enhances hardenability by segregating at the austenite grain boundaries. Also, B is an element that inhibits the formation and grain growth of ferrite during cooling after annealing. To obtain such effects, the B content is preferably 0.0001% or more. The B content is more preferably 0.0002% or more. The B content is more preferably 0.0005% or more, and even more preferably 0.0007% or more. On the other hand, if the B content exceeds 0.0100%, cracks may occur inside the steel sheet during hot rolling. In addition, after the steel sheet is punched or V-bended in the V-VDA bending test, the amount of voids generated increases, and the desired λ and S are not obtained. Fmax may not be able to achieve. Therefore, when B is contained, the B content is preferably 0.0100% or less, and more preferably 0.0050% or less.

[0041] Cr:1.000% or less Since Cr is an element that enhances hardenability, the addition of Cr produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To obtain such effects, the Cr content is preferably 0.0005% or more. The Cr content is more preferably 0.010% or more. The Cr content is more preferably 0.030% or more, and even more preferably 0.050% or more. On the other hand, if the Cr content exceeds 1.000%, the area ratio of hard fresh martensite increases excessively, and in the hole expansion test, VDA bending test or V-VDA bending test, the fresh martensite becomes the starting point for void generation, and the desired λ, α and S are not obtained. Fmax Therefore, when Cr is contained, the Cr content is preferably 1.000% or less. The Cr content is more preferably 0.800% or less, and further preferably 0.700% or less.

[0042] Ni: 1.000% or less Since Ni is an element that enhances hardenability, the addition of Ni produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To obtain such effects, the Ni content is preferably 0.005% or more. The Ni content is more preferably 0.020% or more. The Ni content is further preferably 0.040% or more, and even more preferably 0.060% or more. On the other hand, when the Ni content exceeds 1.000%, the area ratio of fresh martensite increases excessively, and in the hole expansion test, VDA bending test or V-VDA bending test, the fresh martensite becomes the starting point for void generation, and the desired λ, α and S are not obtained. Fmax Therefore, when Ni is contained, the Ni content is preferably 1.000% or less, and more preferably 0.800% or less. The Ni content is more preferably 0.600% or less, and even more preferably 0.400% or less.

[0043] Mo: 1.000% or less Mo is an element that enhances hardenability, so the addition of Mo produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To achieve this effect, the Mo content is preferably 0.010% or more. The Mo content is more preferably 0.030% or more. On the other hand, if the Mo content exceeds 1.000%, the area fraction of fresh martensite increases excessively, and in the hole expansion test, VDA bending test or V-VDA bending test, the fresh martensite becomes the starting point for void generation, and the desired λ, α and S are not obtained. Fmax Therefore, when Mo is contained, the Mo content is preferably 1.000% or less. The Mo content is more preferably 0.500% or less, further preferably 0.450% or less, and even more preferably 0.400% or less. The Mo content is more preferably 0.350% or less, and even more preferably 0.300% or less.

[0044] Sb: 0.200% or less Sb is an element that is effective in suppressing the diffusion of C near the steel sheet surface during annealing and controlling the formation of a soft layer near the steel sheet surface. If the soft layer increases excessively near the steel sheet surface, it becomes difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. Therefore, the Sb content is preferably 0.002% or more. The Sb content is more preferably 0.005% or more. On the other hand, if the Sb content exceeds 0.200%, a soft layer is not formed near the steel sheet surface, which may lead to a decrease in hole expandability and bendability. Therefore, when Sb is contained, the Sb content is preferably 0.200% or less. The Sb content is more preferably 0.020% or less.

[0045] Sn: 0.200% or less Like Sb, Sn is an element that is effective in suppressing the diffusion of C near the steel sheet surface during annealing and controlling the formation of a soft layer near the steel sheet surface. If the soft layer increases excessively near the steel sheet surface, it becomes difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. Therefore, the Sn content is preferably 0.002% or more. The Sn content is more preferably 0.005% or more. On the other hand, if the Sn content exceeds 0.200%, a soft layer is not formed near the steel sheet surface, which may lead to a decrease in hole expandability and bendability. Therefore, when Sn is contained, the Sn content is preferably 0.200% or less. The Sn content is more preferably 0.020% or less.

[0046] Cu:1.000% or less Since Cu is an element that enhances hardenability, the addition of Cu produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To obtain such effects, the Cu content is preferably 0.005% or more. The Cu content is more preferably 0.008% or more, and even more preferably 0.010% or more. The Cu content is more preferably 0.020% or more. On the other hand, when the Cu content exceeds 1.000%, the area ratio of fresh martensite increases excessively, and a large amount of coarse precipitates and inclusions may be formed. In such a case, the desired λ, α and S are not obtained, which are the starting points of voids and cracks during hole expansion tests, VDA bending tests or V-VDA bending tests. Fmax Therefore, when Cu is contained, the Cu content is preferably 1.000% or less, and more preferably 0.200% or less.

[0047] Ta:0.100% or less Ta, like Ti, Nb and V, increases TS and YS by forming fine carbides, nitrides or carbonitrides during hot rolling or annealing. In addition, Ta partially dissolves in Nb carbides or Nb carbonitrides to generate composite precipitates such as (Nb,Ta)(C,N). This inhibits the coarsening of precipitates and stabilizes precipitation strengthening. This further improves TS and YS. To obtain such effects, the Ta content is preferably 0.001% or more. The Ta content is more preferably 0.002% or more, and even more preferably 0.004% or more. On the other hand, if the Ta content exceeds 0.100%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of cracks during the hole expansion test, VDA bend test, or V-VDA bend test, and the desired λ, α, and S may not be obtained. Fmax Therefore, when Ta is contained, the Ta content is preferably 0.100% or less. The Ta content is more preferably 0.090% or less, and even more preferably 0.080% or less.

[0048] W: 0.500% or less W is an element that enhances hardenability, so the addition of W produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To achieve this effect, the W content is preferably 0.001% or more. The W content is more preferably 0.030% or more. On the other hand, if the W content exceeds 0.500%, the area ratio of hard fresh martensite increases excessively, and in the hole expansion test, VDA bending test or V-VDA bending test, the fresh martensite becomes the starting point for void generation, and the desired λ, α and S are not obtained. Fmax Therefore, when W is contained, the W content is preferably 0.500% or less. The W content is more preferably 0.450% or less, and further preferably 0.400% or less. The W content is even more preferably 0.300% or less.

[0049] Mg: 0.0200% or less Mg is an element that is effective in making the shape of inclusions such as sulfides and oxides spherical and improving the hole expandability of steel sheets. To obtain such effects, the Mg content is preferably 0.0001% or more. The Mg content is more preferably 0.0005% or more, and even more preferably 0.0010% or more. On the other hand, if the Mg content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of cracks during the hole expansion test, VDA bend test, or V-VDA bend test, and the desired λ, α, and S may not be obtained. Fmax Therefore, when Mg is contained, the Mg content is preferably 0.0200% or less, more preferably 0.0180% or less, and further preferably 0.0150% or less.

[0050] Zn: 0.0200% or less Zn is an element that is effective in making the shape of inclusions spherical and improving the hole expandability of the steel sheet. To obtain such an effect, the Zn content is preferably 0.0010% or more. The Zn content is more preferably 0.0020% or more, and even more preferably 0.0030% or more. On the other hand, if the Zn content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of cracks during the hole expansion test, VDA bend test, or V-VDA bend test, and the desired λ, α, and S may not be obtained. Fmax Therefore, when Zn is contained, the Zn content is preferably 0.0200% or less, more preferably 0.0180% or less, and further preferably 0.0150% or less.

[0051] Co:0.0200% or less Like Zn, Co is an element that is effective in making the shape of inclusions spherical and improving the hole expandability of steel sheets. To obtain such effects, the Co content is preferably 0.0010% or more. The Co content is more preferably 0.0020% or more, and even more preferably 0.0030% or more. On the other hand, if the Co content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of cracks during the hole expansion test, VDA bending test, or V-VDA bending test, and the desired λ, α, and S may not be obtained. Fmax Therefore, when Co is contained, the Co content is preferably 0.0200% or less, more preferably 0.0180% or less, and further preferably 0.0150% or less.

[0052] Zr: 0.1000% or less Like Zn and Co, Zr is an element that is effective in making the shape of inclusions spheroidal and improving the hole expandability of steel sheets. To obtain such an effect, the Zr content is preferably 0.0010% or more. On the other hand, if the Zr content exceeds 0.1000%, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of cracks during a hole expanding test, a VDA bending test, or a V-VDA bending test, and the desired λ, α, and S may not be obtained. Fmax Therefore, when Zr is contained, the Zr content is preferably 0.1000% or less. The Zr content is more preferably 0.0300% or less, and further preferably 0.0100% or less.

[0053] Ca:0.0200% or less Ca exists as inclusions in steel. If the Ca content exceeds 0.0200%, a large amount of coarse inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of cracks during hole expansion tests, VDA bend tests, or V-VDA bend tests, and the desired λ, α, and S may not be obtained. Fmax Therefore, when Ca is contained, the Ca content is preferably 0.0200% or less. The Ca content is preferably 0.0020% or less. The Ca content is more preferably 0.0019% or less, and further preferably 0.0018% or less. Although there is no particular lower limit for the Ca content, the Ca content is preferably 0.0005% or more, and more preferably 0.0010% or more due to restrictions on production technology.

[0054] Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, REM: 0.0200% or less Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are all elements effective for improving the hole expandability of steel sheet. In order to obtain such effects, the contents of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are each preferably 0.0001% or more. On the other hand, when the contents of Se, Te, Ge, Sr, Cs, Hf, Pb, Bi and REM exceed 0.0200% respectively, and when the content of As exceeds 0.0500%, respectively, a large amount of coarse precipitates and inclusions may be generated. In such cases, the coarse precipitates and inclusions may become the starting points of cracks during the hole expansion test, VDA bend test or V-VDA bend test, and the desired λ, α and S may not be obtained. Fmax Therefore, when at least one of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi, and REM is contained, the contents of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi, and REM are each preferably 0.0200% or less, and the content of As is preferably 0.0500% or less. The Se content is more preferably 0.0005% or more, and further preferably 0.0008% or more.The Se content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Te content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Te content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Ge content is more preferably 0.0005% or more, and further preferably 0.0008% or more.The Ge content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The As content is more preferably 0.0010% or more, and further preferably 0.0015% or more.The As content is more preferably 0.0400% or less, and further preferably 0.0300% or less. The Sr content is more preferably 0.0005% or more, and further preferably 0.0008% or more.The Sr content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Cs content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Cs content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Hf content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Hf content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Pb content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Pb content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The Bi content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The Bi content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. The REM content is more preferably 0.0005% or more, and even more preferably 0.0008% or more.The REM content is more preferably 0.0180% or less, and even more preferably 0.0150% or less. In the present invention, REM refers to scandium (Sc), which has atomic number 21, yttrium (Y), which has atomic number 39, and lanthanoids ranging from lanthanum (La), which has atomic number 57, to lutetium (Lu), which has atomic number 71. In the present invention, the REM concentration refers to the total content of one or more elements selected from the above-mentioned REM. The REM is not particularly limited, but is preferably Sc, Y, Ce, or La.

[0055] That is, the base steel sheet of the steel sheet according to one embodiment of the present invention is, in mass%, C: 0.050% or more and 0.400% or less, Si: more than 0.75% and 3.00% or less, Mn: 2.00% or more and less than 3.50%, P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% or more and 2.000% or less, and N: 0.0100% or less, and optionally Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1. The composition is at least one selected from the group consisting of Fe: 0.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM: 0.0200% or less, with the balance being Fe and unavoidable impurities.

[0056] steel structure Next, the steel structure of the base steel sheet of the steel sheet according to one embodiment of the present invention will be described. The steel structure of the base steel sheet of the steel sheet according to one embodiment of the present invention has an area ratio of bainitic ferrite: 3.0% or more and 20.0% or less, an area ratio of tempered martensite (excluding retained austenite): 40.0% or more and 90.0% or less, a volume ratio of retained austenite: more than 3.0% and 15.0% or less, a carbon concentration in the retained austenite: 0.60 mass% or more and 1.30 mass% or less, an area ratio of fresh martensite: 10.0% or less (including 0.0%), and a density of carbides in the tempered martensite of 8.0 particles / μm 2the amount of diffusible hydrogen in the base steel sheet is 0.50 ppm by mass or less, and further, when a V-VDA bending test is performed up to the maximum load point, the length of the crack in the L cross section is 400 μm or less, and further, in a region formed at a position up to 50 μm on each side of the starting line perpendicular to the starting line from each position starting at the outer bend apex of the VDA bend, the ratio of the average grain size in the thickness direction of bainitic ferrite before processing to the average grain size after processing is 5.0 or less.

[0057] The reasons for each limitation will be explained below.

[0058] Area ratio of bainitic ferrite: 3.0% to 20.0% Bainitic ferrite has intermediate hardness compared to soft ferrite and hard fresh martensite, and is an important phase for ensuring good hole expansion, bendability, bending fracture properties, and axial crush properties. Bainitic ferrite is also a useful phase for obtaining an appropriate amount of area fraction of retained austenite and carbon concentration in the retained austenite by utilizing the diffusion of C from bainitic ferrite to untransformed austenite. Therefore, the area fraction of bainitic ferrite is set to 3.0% or more. The area ratio of bainitic ferrite is preferably 5.0% or more, and more preferably 8.0% or more. On the other hand, if the area ratio of bainitic ferrite is excessively increased, the strength decreases and the area ratio of retained austenite exceeds a predetermined amount, so the area ratio of bainitic ferrite is set to 20.0% or less. The area ratio of bainitic ferrite is preferably 18.0% or less, and more preferably 15.0% or less. Bainitic ferrite is upper bainite with little carbide that is formed in a relatively high temperature range.

[0059] Area ratio of tempered martensite (excluding retained austenite): 40.0% to 90.0% Tempered martensite has intermediate hardness compared to soft ferrite and hard fresh martensite, and is an important phase for ensuring good hole expansion property, bendability, bending fracture property, and axial crush property. Tempered martensite is also effective for improving TS. Therefore, the area ratio of tempered martensite is set to 40.0% or more. The area ratio of tempered martensite is preferably 60.0% or more. On the other hand, if the area ratio of tempered martensite increases excessively, ductility decreases. Therefore, the area ratio of tempered martensite is set to 90.0% or less. The area ratio of tempered martensite is preferably 85.0% or less, and more preferably 80.0% or less.

[0060] Area ratio of retained austenite: More than 3.0% and less than 15.0% From the viewpoint of obtaining good ductility, the area ratio of the retained austenite is set to be more than 3.0%. The area ratio of the retained austenite is preferably 5.0% or more. On the other hand, if the area ratio of the retained austenite is excessively increased, when the steel sheet is subjected to punching in a hole expansion test or V-bending in a V-VDA test, fresh martensite formed by deformation-induced transformation becomes the starting point of void formation, and the desired λ and S are not obtained. Fmax Therefore, the area ratio of the retained austenite is set to 15.0% or less. The area ratio of the retained austenite is preferably 12.0% or less, and more preferably 10.0% or less.

[0061] For example, the area ratio of retained austenite can be suppressed to 15.0% or less by controlling the tension during the second cooling step in the manufacturing method described later. 2By applying the above tension at least once, and then performing a process of applying four or more passes while the steel sheet is in contact with rolls having a diameter of 500 mm or more and 1500 mm or less for 1 / 4 of the roll circumference per pass, and a process of applying two or more passes while the steel sheet is in contact with rolls having a diameter of 500 mm or more and 1500 mm or less for 1 / 2 of the roll circumference per pass, unstable retained austenite undergoes processing-induced transformation to become fresh martensite, which is then tempered during cooling, and finally becomes tempered martensite.

[0062] Carbon concentration in retained austenite: 0.60% by mass or more and 1.30% by mass or less The carbon concentration in the retained austenite is an index that affects the stability of the transformation of the retained austenite into martensite during deformation. If the carbon concentration in the retained austenite is less than 0.60 mass%, the retained austenite is unstable, and after stress is applied, deformation-induced martensite transformation occurs before plastic deformation, making it impossible to obtain the required elongation. On the other hand, if the carbon concentration in the retained austenite exceeds 1.30 mass%, the hardness of fresh martensite formed from the retained austenite when the steel plate is punched in a hole expansion test or V-bended in a V-VDA test increases significantly, promoting the generation and connection of voids, and decreasing the desired λ and S. Fmax Therefore, the carbon concentration in the retained austenite is set to 0.60 mass% or more and 1.30 mass% or less. The carbon concentration in the retained austenite is preferably set to 0.80 mass% or more. In addition, the carbon concentration in the retained austenite is preferably set to 1.20 mass% or less.

[0063] Area ratio of fresh martensite: 10.0% or less (including 0.0%) If the area fraction of fresh martensite increases excessively, the fresh martensite becomes the starting point for void formation in the hole expansion test, VDA bending test, or V-VDA bending test, and the desired λ, α, and S are not obtained. Fmaxcannot be achieved. In addition, as the area ratio of fresh martensite increases, the amount of diffusible hydrogen in the steel sheet increases, further deteriorating the hole expandability and bendability. From the viewpoint of ensuring good hole expandability and bendability, the area ratio of fresh martensite is set to 10.0% or less, preferably 5.0% or less. The lower limit of the area ratio of fresh martensite is not particularly limited, and may be 0.0%. It should be noted that fresh martensite is martensite that has been quenched (not tempered).

[0064] Density (number density) of carbides in tempered martensite: 8.0 particles / μm 2 below In the present invention, the density of carbides in the tempered martensite is 8.0 pieces / μm 2 Above this value, the number of voids caused by carbides increases in the hole expansion test, VDA bend test or V-VDA bend test, promoting the initiation and propagation of cracks, resulting in the desired λ, α and S values. Fmax Therefore, the density of carbides in the tempered martensite is 8.0 / μm 2 The density of carbides in the tempered martensite is preferably 7.0 particles / μm 2 More preferably, it is 6.0 particles / μm or less. 2 The following is the result. Although there is no particular lower limit, the density of carbides in the tempered martensite is preferably 1.0 carbide / μm 2 More preferably, it is 2.0 particles / μm or more. 2 That's all.

[0065] The remaining structure other than the above includes, for example, carbides such as ferrite, lower bainite, pearlite, cementite, etc. In order to ensure a TS of 1180 MPa or more and a high YS, the area ratio of pearlite is preferably 5.0% or less. The type of the remaining structure can be confirmed, for example, by observation with a SEM (Scanning Electron Microscope).

[0066] The area ratios of bainitic ferrite, tempered martensite and hard second phase (retained austenite + fresh martensite) are measured at a 1 / 4 position in the sheet thickness of the base steel sheet as follows. That is, a sample is cut out from the base steel sheet so that the cross section of the sheet thickness parallel to the rolling direction of the base steel sheet becomes the observation surface. The observation surface of the sample is then mirror-polished using diamond paste. The observation surface of the sample is then finish-polished using colloidal silica, and etched with 3 vol.% nital to reveal the structure. Then, three fields of view of 25.6 μm×17.6 μm on the observation surface of the sample are photographed using a SEM (Scanning Electron Microscope) under conditions of an acceleration voltage of 15 kV and a magnification of 5000 times. From the obtained structural image, bainitic ferrite, tempered martensite, hard second phase (retained austenite + fresh martensite) and remaining structure are identified as follows.

[0067] Bainitic ferrite: This is a region that is black to dark gray in color and has a massive or amorphous shape. It also contains no iron carbides or contains a relatively small amount of them. Tempered martensite: This is a gray area with an amorphous shape. It also contains a relatively large number of iron-based carbides. Hard second phase (retained austenite + fresh martensite): This is a region that is white to light gray in color and has an amorphous form. It does not contain iron-based carbides. If the size is relatively large, the color gradually darkens as it moves away from the interface with other structures, and the interior may be dark gray. Ferrite: A black region with a blocky shape. It contains almost no iron-based carbides. However, if iron-based carbides are contained, the area of ​​the ferrite includes the area of ​​the iron-based carbides. The same applies to the bainitic ferrite and tempered martensite mentioned above. Cementite: White areas that are dotted or linear in shape. They are included in tempered martensite, bainitic ferrite, and ferrite. Lower bainite, pearlite, etc.: The morphology of these is well known.

[0068] Next, the area of ​​each phase identified in the structural image is calculated by the following method. An equally spaced 20 x 20 grid is placed on an area of ​​23.1 μm x 17.6 μm in actual length on the 5000x magnification SEM image, and the area ratios of bainitic ferrite, tempered martensite, and hard second phase are calculated by the point counting method, which counts the number of points on each phase. The area ratios are calculated as the average of three area ratios determined on separate 5000x magnification SEM images.

[0069] The area ratio of retained austenite is measured as follows. That is, the base steel plate is mechanically ground in the plate thickness direction (depth direction) to a position of 1 / 4 of the plate thickness, and then chemically polished with oxalic acid to obtain the observation surface. The observation surface is then observed by X-ray diffraction. MoKα rays are used as the incident X-rays, and the ratio of the diffraction intensity of the (200), (211), and (220) faces of the fcc iron (austenite) to the diffraction intensity of the (200), (220), and (311) faces of the bcc iron is calculated, and the volume fraction of the retained austenite is calculated from the ratio of the diffraction intensity of each face. The retained austenite is then considered to be three-dimensionally homogeneous, and the volume fraction of the retained austenite is taken as the area fraction of the retained austenite.

[0070] Regarding the distribution of the carbon concentration in the retained austenite, the lattice constant of the retained austenite is calculated using the diffraction peak of the (220) plane of fcc iron (austenite) measured by the above-mentioned X-ray diffraction method. Then, the carbon concentration in the retained austenite is calculated by the following formula. Cγ=((A-(3.572+0.0012×[Mn%]-0.00157×[Si%]+0.0056×[Al%])) / 0.033 Where, A: lattice constant of retained austenite, Cγ: carbon concentration in retained austenite, [Mn%], [Si%], and [Al%]: the Mn, Si, and Al contents (mass%) in the steel plate, respectively.

[0071] The area ratio of fresh martensite is determined by subtracting the area ratio of retained austenite from the area ratio of the hard second phase determined as described above. [Area ratio of fresh martensite (%)] = [Area ratio of hard second phase (%)] - [Area ratio of retained austenite (%)]

[0072] The area ratio of the remaining structure is determined by subtracting the area ratio of bainitic ferrite, the area ratio of tempered martensite, and the area ratio of the hard second phase determined as described above from 100.0%. [Area ratio of remaining structure (%)] = 100.0 - [Area ratio of bainitic ferrite (%)] - [Area ratio of tempered martensite (%)] - [Area ratio of hard second phase (%)]

[0073] The density of carbides in tempered martensite is measured as follows. The SEM structural image used in the above structural fraction measurement is hand-painted to extract the tempered martensite and carbides by color coding, and the image is taken to be of only tempered martensite or carbides. Here, carbides with a diameter (circle equivalent diameter) of 100 nm or more are the target. The open source ImageJ is then used to determine the area of ​​the tempered martensite and the number of carbides in the tempered martensite. The number of carbides in the tempered martensite divided by the area of ​​the tempered martensite is the density of the carbides in the tempered martensite, and the average value of 10 tempered martensites randomly extracted from separate SEM images is taken to be the density of the carbides in the tempered martensite. In addition, with regard to one carbide, a granular region in an SEM image that is surrounded by tempered martensite and formed integrally without interruption is counted as one carbide.

[0074] Diffusible hydrogen content: 0.50 mass ppm or less From the viewpoint of obtaining better hole expandability and bendability, the diffusible hydrogen content of the base steel sheet is preferably 0.50 ppm by mass or less. The diffusible hydrogen content of the base steel sheet is more preferably 0.30 ppm by mass or less. The lower limit of the diffusible hydrogen content of the base steel sheet is not particularly specified and may be 0 ppm by mass. In addition, due to constraints on production technology, the diffusible hydrogen content of the base steel sheet is more preferably 0.01 ppm by mass or more.

[0075] Here, the amount of diffusible hydrogen in the base steel sheet is measured as follows. A test piece having a length of 30 mm and a width of 5 mm is taken from the steel sheet, and if a zinc plating layer is formed on the steel sheet, the zinc plating layer is removed with an alkali. Next, the amount of hydrogen released from the test piece is measured by thermal desorption analysis. Specifically, the test piece is continuously heated from room temperature (-5 to 55°C) to 300°C at a heating rate of 200°C / h, and then cooled to room temperature. At this time, the amount of hydrogen (accumulated amount of hydrogen) released from the test piece in the temperature range from room temperature to 210°C during the continuous heating is measured. Then, the measured amount of hydrogen is divided by the mass of the test piece (the test piece after the zinc plating layer is removed and before the continuous heating) and the value converted to mass ppm is defined as the diffusible hydrogen amount of the base steel sheet. The measurement of the amount of diffusible hydrogen is preferably performed after the production of the steel sheet is completed. It is more preferable to measure the amount of hydrogen within one week after the production of the steel sheet is completed. In addition, taking into consideration production in various countries around the world, the room temperature should be within the range of local temperature changes over the course of a year. In general, a range of 10 to 50°C is preferable.

[0076] In addition, for products (components) after steel plate has been formed or joined, test pieces are cut out from the product in a typical usage environment and the diffusible hydrogen content of the base steel plate is measured in the same manner as above. If the value is 0.50 ppm by mass or less, it can be deemed that the diffusible hydrogen content of the base steel plate of the steel plate at the material stage before forming or joining was also 0.50 ppm by mass or less.

[0077] surface soft layer In the base steel sheet of the steel sheet according to one embodiment of the present invention, it is preferable that the base steel sheet has a soft surface layer on its surface. The soft surface layer contributes to suppressing bending crack propagation during press forming and vehicle body collision, thereby further improving bending fracture resistance. The soft surface layer means a decarburized layer, and is a surface region having a Vickers hardness of 85% or less of the Vickers hardness of the cross section at 1 / 4 of the plate thickness. Here, the soft surface layer is formed in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction. The region in which the soft surface layer is formed is preferably 150 μm or less, more preferably 120 μm or less, from the surface of the base steel sheet in the sheet thickness direction. There is no particular lower limit for the thickness of the soft surface layer, but the thickness of the soft surface layer is preferably 8 μm or more, more preferably 11 μm or more. The soft surface layer is preferably 30 μm or more, more preferably 40 μm or more. The 1 / 4 sheet thickness position of the base steel sheet where the Vickers hardness is measured is a non-surface soft layer (a layer that does not satisfy the hardness conditions of the surface soft layer defined in the present invention). Vickers hardness is measured based on JIS Z 2244-1 (2020) at a load of 10 gf.

[0078] Nano-hardness of the soft surface layer When the nano hardness is measured at 300 or more points in a 50 μm × 50 μm area on the sheet surface at 1 / 4 of the sheet thickness depth and 1 / 2 of the sheet thickness depth from the surface of the base steel sheet, the ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at 1 / 4 of the sheet thickness depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at 1 / 4 of the sheet thickness depth of the soft surface layer is 0.10 or less. In the present invention, in order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, when the nanohardness is measured at 300 or more points in a 50 μm×50 μm region on the sheet surface at each of the 1 / 4 position and the 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, it is preferable that the ratio of the number of measurements of nanohardness of 7.0 GPa or more at the 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 0.10 or less to the total number of measurements at the 1 / 4 position of the sheet thickness direction depth of the soft surface layer. When the ratio of nanohardness of 7.0 GPa or more is 0.10 or less, it means that the ratio of hard structure (martensite, etc.), inclusions, etc. is small, and it is possible to further suppress the generation and connection of voids and crack growth in hard structure (martensite, etc.) and inclusions during press forming and collision, and to obtain excellent R / t, α and S. Fmax is obtained.

[0079] The standard deviation σ of the nano hardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nano hardness of the sheet surface at 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less. In the present invention, in order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, it is preferable that the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less. When the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 4 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 1.8 GPa or less, and further, the standard deviation σ of the nanohardness of the sheet surface at a position 1 / 2 of the sheet thickness direction depth of the soft surface layer from the steel sheet surface is 2.2 GPa or less, it means that the microstructural hardness difference is small, and since the microstructural hardness difference is small, it is possible to further suppress the generation and connection of voids and the propagation of cracks during press forming or collision, and excellent R / t, α and S are obtained. Fmax is obtained. A preferred range of the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.7 GPa or less. The standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is more preferably 1.3 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nanohardness of the sheet surface at 1 / 4 of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet may be 0.5 GPa or more. A more preferred range of the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.1 GPa or less. The standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is more preferably 1.7 GPa or less. Although there is no particular lower limit, the standard deviation σ of the nanohardness of the sheet surface at 1 / 2 the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet may be 0.6 GPa or more.

[0080] Here, the nano-hardness of the plate surface at the 1 / 4 and 1 / 2 positions in the plate thickness direction depth is a hardness measured by the following method. When a plating layer is formed, after peeling off the plating layer, mechanical polishing is performed from the surface of the base steel sheet to a position 5 μm away from the surface of the base steel sheet, which is 1 / 4 of the way down to the soft surface layer, buffing with diamond and alumina is performed from the surface of the base steel sheet to a position 1 / 4 of the way down to the soft surface layer, and colloidal silica polishing is further performed. Here, the plating layer to be peeled off is the zinc plating layer if a zinc plating layer is formed, the metal plating layer if a metal plating layer is formed, and the zinc plating layer and the metal plating layer if both a zinc plating layer and a metal plating layer are formed. Using Hysitron's tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the following conditions: load: 500 μN, measurement area: 50 μm × 50 μm, and impact spacing: 2 μm. Next, the surface soft layer is mechanically polished up to 1 / 2 the depth in the plate thickness direction, buffed with diamond and alumina, and polished with colloidal silica. Using a Hysitron tribo-950, the nano hardness is measured with a Berkovich-shaped diamond indenter under the following conditions: load: 500 μN, measurement area: 50 μm × 50 μm, and impact spacing: 2 μm. Nano hardness is measured at 300 or more points at a position 1 / 4 of the way through the plate thickness, and also at 300 or more points at a position 1 / 2 of the way through the plate thickness. For example, if the thickness of the surface soft layer is 100 μm, the 1 / 4 position is 25 μm from the surface of the surface soft layer, and the 1 / 2 position is 50 μm from the surface of the surface soft layer. At this 25 μm position, nano hardness is measured at 300 or more points, and also at the 50 μm position, nano hardness is measured at 300 or more points.

[0081] Metal plating layer (first plating layer) Furthermore, the steel sheet according to one embodiment of the present invention preferably has a metal plating layer (first plating layer, pre-plating layer) (note that the metal plating layer (first plating layer) excludes a galvanized layer such as a hot-dip galvanized layer or a galvannealed hot-dip galvanized layer) on one or both surfaces of the base steel sheet. The metal plating layer is preferably a metal electroplated layer, and the following description will be given taking a metal electroplated layer as an example. By forming a metal electroplating layer on the surface of the steel sheet, the outermost metal electroplating layer contributes to suppressing the occurrence of bending cracks during press forming and vehicle collisions, thereby further improving bending fracture resistance. In the present invention, the thickness of the soft layer can be increased and the axial collapse characteristics can be made very excellent by setting the dew point to above -5°C. In this regard, in the present invention, by having a metal plating layer, the dew point is set to -5°C or less, and even if the soft layer thickness is small, the axial collapse characteristics can be obtained that are equivalent to those in the case of a thick soft layer.

[0082] Metal species of the metal electroplating layer include Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, PtThe metal may be any of Au, Hg, Ti, Pb, and Bi, but Fe is more preferable. In the following, an Fe-based electroplating layer will be described as an example, but the following conditions for Fe can be similarly adopted for other metals.

[0083] The adhesion weight of the Fe-based electroplating layer is 0g / m 2 More than 2.0 g / m 2 The upper limit of the coating weight of the Fe-based electroplating layer per side is not particularly limited, but from the viewpoint of cost, the coating weight of the Fe-based electroplating layer per side is set to 60 g / m or more. 2 The coating weight of the Fe-based electroplating layer is preferably 50 g / m 2 More preferably, it is 40 g / m or less. 2 More preferably, it is 30 g / m or less. 2 The following applies.

[0084] The adhesion weight of the Fe-based electroplating layer is measured as follows. A 10 x 15 mm sample is taken from the Fe-based electroplated steel sheet and embedded in resin to create a cross-section embedded sample. Three random locations on the cross-section are observed using a scanning electron microscope (SEM) at an accelerating voltage of 15 kV and a magnification of 2000 to 10000 times depending on the thickness of the Fe-based plating layer, and the average thickness of the three fields of view is multiplied by the specific gravity of iron to convert it into the adhesion weight of the Fe-based electroplating layer per side.

[0085] As the Fe-based electroplating layer, in addition to pure Fe, alloy plating layers such as Fe-B alloy, Fe-C alloy, Fe-P alloy, Fe-N alloy, Fe-O alloy, Fe-Ni alloy, Fe-Mn alloy, Fe-Mo alloy, Fe-W alloy, etc. can be used. The composition of the Fe-based electroplating layer is not particularly limited, but it is preferable that the composition contains one or more elements selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V and Co in a total of 10 mass% or less, with the balance being Fe and unavoidable impurities. By making the amount of elements other than Fe 10 mass% or less in total, it is possible to prevent a decrease in electrolysis efficiency and form the Fe-based electroplating layer at low cost. In the case of the Fe-C alloy, the content of C is preferably 0.08 mass% or less.

[0086] It is more preferable to have a surface soft layer under the Fe-based electroplated layer, which can significantly improve bending fracture resistance. When an Fe-based electroplated layer is present, the Vickers hardness distribution is measured in the sheet thickness direction from the interface between the Fe-based electroplated layer and the base steel sheet using the above-mentioned method, and the depth in the sheet thickness direction of the surface soft layer is evaluated.

[0087] V-VDA bending test is performed up to the maximum load point, and the crack length at the L cross section is 400μm or less. In the present invention, in a steel sheet having a crack length exceeding 400 μm, voids in the steel sheet structure are rapidly formed and propagated, and bending fracture resistance is deteriorated. Therefore, the crack length is set to 400 μm or less. The crack length is preferably 300 μm or less, and more preferably 200 μm or less. The lower limit is not particularly limited, but this value may be 0 μm.

[0088] A V-VDA bending test is performed up to the maximum load point, and in the L cross section, from each position of the start line that exists from the outer bend apex of the VDA bend to a position 50 μm in the plate thickness direction, the ratio of the average grain size of bainitic ferrite in the plate thickness direction before processing to the average grain size after processing (change in average grain size before and after processing) is 5.0 or less. Next, the amount of change in the grain size of the bainitic ferrite in the sheet thickness direction before and after processing will be described. In Fig. 1, BF denotes bainitic ferrite, F denotes ferrite, and TM denotes tempered martensite. In Fig. 1, θ(TM) denotes carbides in tempered martensite, H1 denotes a hard second phase, and X1(BF) denotes an island-like second phase in the bainitic ferrite. As shown in FIG. 1, the bainitic ferrite BF in the steel sheet structure forms island-shaped retained austenite inside due to carbon distribution. When the bainitic ferrite BF is deformed by processing, voids are likely to occur at the boundary between the bainitic ferrite BF and the hard fresh martensite formed by processing-induced transformation of the island-shaped retained austenite. If the change in the average grain size in the sheet thickness direction of the bainitic ferrite BF before and after processing exceeds 5.0, the bainitic ferrite BF is subjected to tensile stress in the rolling direction, and the increase in the number of voids promotes the generation and propagation of cracks, resulting in a decrease in bending fracture resistance. Therefore, the change in the average grain size in the sheet thickness direction of the bainitic ferrite before and after processing is set to 5.0 or less. The change is preferably 4.8 or less, more preferably 4.5 or less. Furthermore, if the change in the average grain size of bainitic ferrite before and after processing is less than 0.2, voids may easily occur at the boundary between the island-shaped retained austenite inside the bainitic ferrite and the hard fresh martensite formed by processing-induced transformation in the bainitic ferrite subjected to compressive stress, and bending fracture resistance may decrease. Therefore, the change in the average grain size in the sheet thickness direction of bainitic ferrite before and after processing is preferably 0.2 or more. The change is preferably 0.3 or more, and more preferably 0.5 or more.

[0089] The above V-VDA bending test is carried out as follows. A 60mm x 65mm test piece is taken from the obtained steel plate by shearing. Here, the 60mm side is parallel to the rolling (L) direction. The test piece is prepared by bending the steel plate 90° (primary bending) in the rolling (L) direction with the width (C) direction as the axis at a curvature radius / plate thickness of 4.2. In the 90° bending (primary bending), as shown in Figure 2-1(a), a punch B1 is pressed into the steel plate placed on a die A1 having a V groove to obtain a test piece T1. Next, as shown in Figure 2-1(b), a punch B2 is pressed into the test piece T1 placed on a support roll A2 so that the bending direction is perpendicular to the rolling direction, to perform an orthogonal bending (secondary bending). In Figures 2-1(a) and 2-1(b), the symbol D1 indicates the width (C) direction, and the symbol D2 indicates the rolling (L) direction. A schematic diagram of the stroke-load curve obtained during the V-VDA test is shown in Figure 3. The V-VDA test is performed up to the maximum load point P, and then the sample is unloaded when the load becomes 94.9 to 99.9% of the maximum load (see symbol R in Figure 3) to be used as the evaluation sample in the V-VDA bending test.

[0090] In the V-VDA bending test, a test piece T1 obtained by subjecting a steel plate to a V-bending process (primary bending process) is shown in FIG. 2-2(c). Also, a test piece T2 obtained by subjecting test piece T1 to a VDA bending process (secondary bending process) is shown in FIG. 2-2(d). The position shown by the dashed line in test piece T2 in FIG. 2-2(d) is the above-mentioned V-bending ridgeline, which corresponds to the position shown by the dashed line in test piece T1 in FIG. 2-2(c) before VDA bending. In the present invention, the overlapping region of the V-bending ridgeline and the VDA bending ridgeline is the VDA bending apex and the center position of the dashed line shown as a in FIG. 2-2(d). Specifically, the V-bend ridgeline refers to the region that is bent in a V-shape and extends in the width direction from the V-shape corner (vertex) to 5 mm on both sides. The region other than the V-shape ridgeline is the V-shape flat portion. The VDA bend ridgeline refers to a region that is VDA bent and extends 5 mm on both sides from the VDA bend corner (vertex) that is provided in the rolling direction. The positional relationship between the L-section AL of the V-bend ridge and the VDA-bend ridge and the test piece T2 is shown by the dotted line in Figure 2-3(e). Figure 2-3(f) shows the L-section AL when the D2 direction is perpendicular to the paper and the D1 direction is parallel to the paper.

[0091] The V-VDA bending test is carried out up to the maximum load point, and the crack length on the L cross section (hereinafter also referred to as the AL surface) in the overlapping region of the V-bend ridgeline and the VDA bend ridgeline is calculated as follows. A specimen is cut from the base steel plate so that the aluminum surface of the steel plate that has been subjected to the V-VDA bending test up to the maximum load point becomes the observation surface. The observation surface of the specimen is then mirror-polished using diamond paste. The observation surface of the specimen is then finish-polished using colloidal silica, and etched with 3 vol.% nital to reveal the structure. Then, using a SEM (Scanning Electron Microscope) with an accelerating voltage of 15 kV and a magnification of 200x, a field of view of 25.6 μm x 17.6 μm is photographed at the bending apex of the observation surface of the sample, with the axis of symmetry of the AL surface perpendicular to the surface, to observe the entire crack. In the obtained image of the crack, the vertical distance between the start point and end point of the crack is defined as the crack length. An example of an image of an actually measured crack is shown in Figure 4. In Figure 4, the symbol D2 indicates the rolling (L) direction, and the symbol D4 indicates the plate thickness direction. The symbol L also indicates the crack length.

[0092] Next, a V-VDA bending test is performed up to the maximum load point, and a method for measuring the change in the average grain size of bainitic ferrite in the sheet thickness direction before and after processing in a region (AB region shown by the dotted line in Figure 2-3 (f), hereinafter also referred to as AB region) of 0 to 50 μm from the steel sheet surface on the outer side of the VDA bend and 50 μm to the left and right of the bend apex of the VDA bend at the L cross section in the overlapping region of the V-bend ridgeline and the VDA bend ridgeline is described. Here, first, the AB region will be described with reference to Fig. 2-4. Fig. 2-4 is a schematic diagram for explaining the AB region. As shown in Fig. 2-4, the AB region refers to a region formed at a position up to 50 μm on each side of the start line L0 in the vertical direction from each position of the start line L0, which exists from the bending vertex t0 on the outer side of the VDA bending as a starting point to a position 50 μm in the sheet thickness direction. The method for measuring the above-mentioned change amount is to first use a sample in which the AL surface is observed after the above-mentioned V-VDA bending test is performed up to the maximum load point (hereinafter also referred to as the deformed sample) and a sample used for measuring the area ratio of the steel sheet structure (hereinafter also referred to as the undeformed sample) to photograph five fields of view of 25.6 μm × 17.6 μm for each sample using a SEM (Scanning Electron Microscope) under conditions of an acceleration voltage of 15 kV and a magnification of 3000 times. For the deformed sample, the inside of the AB region is photographed to observe the bainitic ferrite that has been deformed by processing (hereinafter also referred to as the deformed bainitic ferrite). For the undeformed sample, the area from the surface of the base steel sheet to a position 50 μm into the sheet thickness is photographed to observe the undeformed bainitic ferrite (hereinafter also referred to as the undeformed bainitic ferrite). From the obtained structural images, ten particles each of the bainitic ferrite after deformation and the bainitic ferrite before deformation were randomly selected by hand, and the longest point in the plate thickness direction of each bainitic ferrite was taken as the grain size. The grain sizes in the thickness direction of the 10 pieces of bainitic ferrite after deformation and the 10 pieces of bainitic ferrite before deformation were respectively averaged, and the average grain size in the thickness direction of the bainitic ferrite before deformation was divided by the average grain size in the thickness direction of the bainitic ferrite after deformation (ratio of the average grain size before processing to the average grain size after processing: average grain size before processing (nm) / average grain size after processing (nm)) was used to determine the change in the average grain size in the thickness direction of bainitic ferrite before and after processing. An example of an image of bainitic ferrite before deformation and bainitic ferrite after deformation is shown in Fig. 5. In Fig. 5, the symbol BF1 indicates the bainitic ferrite before deformation, and the symbol BF2 indicates the bainitic ferrite after deformation. With regard to one bainitic ferrite particle, a granular region in an SEM image that is surrounded by other structures and formed continuously and integrally is counted as one particle.

[0093] Next, the mechanical properties of the steel plate according to one embodiment of the present invention will be described.

[0094] Tensile strength (TS): 1180MPa or more The tensile strength TS of the steel plate according to one embodiment of the present invention is 1180 MPa or more. Although there is no particular upper limit, the tensile strength TS is preferably less than 1470 MPa. The yield stress (YS), total elongation (El), limit hole expansion ratio (λ), limit bending angle (α) in a VDA bending test, and stroke at maximum load (S) in a V-VDA bending test of the steel plate according to one embodiment of the present invention are shown in Table 1. Fmax ) and the presence or absence of axial compression fracture are as described above.

[0095] In addition, the tensile strength (TS), yield stress (YS) and total elongation (El) are measured by a tensile test conforming to JIS Z 2241 (2011) described later in the Examples. The limit hole expansion ratio (λ) is measured by a hole expansion test conforming to JIS Z 2256 (2020) described later in the Examples. The limit bending angle (α) in the VDA bending test is measured by a VDA bending test conforming to VDA238-100 described later in the Examples. The stroke (S) at maximum load in the V-VDA bending test is measured by a VDA bending test conforming to VDA238-100 described later in the Examples. Fmax The presence or absence of fracture due to axial compression is measured by an axial compression test described later in the examples.

[0096] Zinc plating layer (second plating layer) A steel sheet according to one embodiment of the present invention may have a zinc plating layer formed on the base steel sheet as the outermost layer (on the surface of the base steel sheet or on the surface of the metal plating layer if a metal plating layer is formed), and this zinc plating layer may be provided on only one surface of the base steel sheet, or on both surfaces. That is, the steel sheet of the present invention may have a base steel sheet on which a second plating layer (zinc plating layer) is formed, or may have a base steel sheet on which a metal plating layer (first plating layer (excluding the second plating layer of the zinc plating layer)) and a second plating layer (zinc plating layer) are formed in that order on the base steel sheet. The steel sheet having a zinc-plated layer may be a zinc-plated steel sheet.

[0097] The galvanized layer referred to here refers to a plating layer containing Zn as a main component (Zn content of 50.0% or more), and examples thereof include a hot-dip galvanized layer and an alloyed hot-dip galvanized layer.

[0098] Here, the hot-dip galvanized layer is preferably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% to 1.0 mass% or less of Al. The hot-dip galvanized layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0 mass% to 3.5 mass%. The Fe content of the hot-dip galvanized layer is more preferably less than 7.0 mass%. The remainder other than the above elements is unavoidable impurities.

[0099] In addition, the galvannealed layer is preferably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% or more and 1.0 mass% or less of Al. In addition, the galvannealed layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0 mass% or more and 3.5 mass% or less. The Fe content of the galvannealed layer is more preferably 7.0 mass% or more, and more preferably 8.0 mass% or more. The Fe content of the galvannealed layer is more preferably 15.0 mass% or less, and more preferably 12.0 mass% or less. The remainder other than the above elements is unavoidable impurities.

[0100] In addition, the coating weight of the zinc-plated layer on one side is not particularly limited, but is preferably 20 g / m 2 The coating weight of the zinc-plated layer on one side is preferably 80 g / m or more. 2 It is preferable that:

[0101] The plating weight of the zinc plating layer is measured as follows. That is, a treatment solution is prepared by adding 0.6 g of a corrosion inhibitor for Fe (Ivit 700BK (registered trademark) manufactured by Asahi Chemical Industry Co., Ltd.) to 1 L of a 10 mass % aqueous hydrochloric acid solution. Next, a steel sheet to be used as a test material is immersed in the treatment solution to dissolve the zinc plating layer. The amount of mass loss of the test material before and after dissolution is then measured, and this value is divided by the surface area of ​​the base steel sheet (the surface area of ​​the part that was covered with plating) to obtain the plating coverage (g / m 2 ) is calculated.

[0102] The thickness of the steel plate according to one embodiment of the present invention is not particularly limited, but is preferably 0.5 mm or more, and more preferably 0.6 mm or more. The plate thickness is more preferably greater than 0.8 mm. The plate thickness is further preferably 0.9 mm or more. The plate thickness is more preferably 1.0 mm or more. The plate thickness is further preferably 1.2 mm or more. The thickness of the steel plate is preferably 3.5 mm or less, and more preferably 2.3 mm or less. The width of the steel plate of the present invention is not particularly limited, but is preferably 500 mm or more, more preferably 750 mm or more, and is preferably 1600 mm or less, more preferably 1450 mm or less.

[0103] [2. Steel plate manufacturing method] Next, a method for manufacturing a steel sheet according to one embodiment of the present invention will be described.

[0104] A method for producing a steel sheet according to one embodiment of the present invention includes a hot rolling process in which a steel slab having the above-mentioned component composition is hot-rolled to produce a hot-rolled steel sheet; a pickling process in which the hot-rolled steel sheet is pickled; an annealing process in which the steel sheet after the pickling process is annealed at an annealing temperature of (Ac1+0.4×(Ac3−Ac1))° C. or more and 900° C. or less for an annealing time of 20 seconds or more; a first cooling process in which the steel sheet after the annealing process is cooled to a first cooling stop temperature of 400° C. or more and 600° C. or less; and a second cooling process in which the steel sheet after the first cooling process is cooled to a second cooling stop temperature of 100° C. or more and 300° C. or less at an average cooling rate of 25.0° C. / second or less, and during the cooling, a pressure of 2.0 kgf / mm is applied to the steel sheet in a temperature range of 300° C. or more and 450° C. or less. 2 a second cooling process in which the steel sheet is subjected to four or more passes while being brought into contact with rolls having a diameter of 500 mm or more and 1500 mm or less for 1 / 4 rotation per pass, and a second cooling process in which the steel sheet is subjected to two or more passes while being brought into contact with rolls having a diameter of 500 mm or more and 1500 mm or less for 1 / 2 rotation per pass; and a reheating process in which the steel sheet after the second cooling process is heated to a tempering temperature in a temperature range of more than 300°C and less than 500°C, and is held in the above temperature range for a tempering time of 20 seconds or more and 900 seconds or less, and during the reheating process, a carbide control parameter CP represented by the following formula (1) is set to 10,000 or more and 15,000 or less, or a cold rolling process in which the steel sheet after the pickling process and before the annealing process is cold rolled to obtain a cold rolled steel sheet. CP=(T+273)×(k+1.2×logt)...Equation (1) where T is the tempering temperature (°C), k is a material constant dependent on the C content, and t is the tempering time (sec). k = -6 × C M +17.8, C M is the carbon content (mass%) in the martensite formed in the second cooling step. Unless otherwise specified, the above temperatures refer to the surface temperatures of the steel slab and the steel plate.

[0105] First, a steel slab having the above-mentioned composition is prepared. For example, a steel material is melted to obtain molten steel having the above-mentioned composition. The melting method is not particularly limited, and known melting methods such as converter melting and electric furnace melting can be used. The obtained molten steel is then solidified to obtain a steel slab. The method for obtaining a steel slab from molten steel is not particularly limited, and for example, a continuous casting method, an ingot casting method, or a thin slab casting method can be used. From the viewpoint of preventing macrosegregation, a continuous casting method is preferred.

[0106] [Hot rolling process] Next, in the hot rolling process, the steel slab is hot rolled to produce a hot rolled steel sheet. The hot rolling may be performed by applying an energy-saving process, such as direct rolling (a method in which the steel slab is not cooled to room temperature, but is charged as a hot piece into a heating furnace and hot rolled) or direct rolling (a method in which the steel slab is briefly kept at a constant temperature and then immediately rolled).

[0107] The hot rolling conditions are not particularly limited, and the hot rolling can be performed, for example, under the following conditions. That is, the steel slab is once cooled to room temperature, and then reheated and rolled. The slab heating temperature (reheating temperature) is preferably 1100°C or higher from the viewpoints of dissolving carbides and reducing the rolling load. In addition, in order to prevent an increase in scale loss, the slab heating temperature is preferably 1300°C or lower. The slab heating temperature is based on the temperature of the steel slab surface.

[0108] Next, the steel slab is subjected to rough rolling according to a conventional method to obtain a rough rolled plate (hereinafter also referred to as a sheet bar). Next, the sheet bar is subjected to finish rolling to obtain a hot rolled steel plate. In addition, when the slab heating temperature is set low, it is preferable to heat the sheet bar using a bar heater or the like before the finish rolling in order to prevent problems during the finish rolling. In order to reduce the rolling load, the finish rolling temperature is preferably set to 800°C or higher. In addition, if the rolling reduction rate in the non-recrystallized state of austenite becomes high, an abnormal structure elongated in the rolling direction may develop, which may reduce the workability of the annealed sheet. Furthermore, by setting the finish rolling temperature to 800°C or higher, the steel structure at the hot rolled steel plate stage and, in turn, the steel structure of the final product are likely to become uniform. In addition, if the steel structure becomes non-uniform, the bendability tends to decrease. On the other hand, if the finish rolling temperature exceeds 950°C, the amount of oxide (scale) generated increases. As a result, the interface between the base steel and the oxide becomes rough, which may deteriorate the surface quality of the steel sheet after pickling and cold rolling. In addition, the crystal grains may become coarse, which may cause a decrease in the strength and bendability of the steel sheet. Therefore, it is preferable that the finish rolling temperature is in the range of 950°C or higher. For the above reasons, it is preferable that the finish rolling temperature is in the range of 800°C or higher and 950°C or higher.

[0109] After the finish rolling, the hot-rolled steel sheet is coiled at a coiling temperature of preferably 450° C. or higher and preferably 750° C. or lower.

[0110] In addition, the sheet bars may be joined together during hot rolling and continuous finish rolling may be performed. Also, the sheet bars may be wound once before the finish rolling. In order to reduce the rolling load during hot rolling, a part or all of the finish rolling may be lubricated rolling. Performing lubricated rolling is also effective from the viewpoint of uniformity of the steel sheet shape and material quality. In addition, the friction coefficient during lubricated rolling is preferably in the range of 0.10 to 0.25. In the hot rolling process, which includes rough rolling and finish rolling, steel slabs are generally made into sheet bars by rough rolling and then into hot rolled steel sheets by finish rolling. However, depending on the mill capacity, etc., such divisions do not matter as long as the specified size is achieved.

[0111] [Pickling process] The hot-rolled steel sheet after the hot rolling process is pickled. Pickling can remove oxides from the steel sheet surface, ensuring good chemical conversion treatment properties and plating quality. Pickling may be performed once or multiple times. There are no particular limitations on the pickling conditions, and the usual methods may be followed.

[0112] [Cold rolling process] Next, the hot-rolled steel sheet is cold-rolled as necessary to obtain a cold-rolled steel sheet. The cold rolling is performed by multi-pass rolling requiring two or more passes, such as tandem multi-stand rolling or reverse rolling. The cold rolling reduction (cumulative reduction) is not particularly limited, but is preferably 20% or more. The cold rolling reduction is preferably 80% or less. If the cold rolling reduction is less than 20%, the steel structure is likely to become coarse and non-uniform in the annealing process, and the TS and bendability of the final product may decrease. On the other hand, if the cold rolling reduction exceeds 80%, the steel sheet is likely to have a defective shape and the amount of zinc coating may become non-uniform. Furthermore, the cold-rolled steel sheet obtained after cold rolling may be optionally subjected to pickling.

[0113] [Metal plating (metal electroplating, first plating) process] In one embodiment of the present invention, a first plating step may be included in which metal plating is applied to one or both sides of the steel sheet after the hot rolling step (after the pickling step, or after the cold rolling step following the pickling step in the case of cold rolling being performed) and before the annealing step to form a metal plating layer (first plating layer). For example, the surface of the hot-rolled steel sheet or cold-rolled steel sheet obtained as described above may be subjected to a metal electroplating treatment to obtain a pre-annealed metal electroplated steel sheet having a pre-annealed metal electroplating layer formed on at least one surface thereof. Note that the metal plating referred to here does not include zinc plating (second plating). The metal electroplating method is not particularly limited, but as described above, it is preferable to form a metal electroplating layer on the base steel sheet, and therefore it is preferable to carry out a metal electroplating process. For example, in the case of an Fe-based electroplating bath, a sulfuric acid bath, a hydrochloric acid bath, or a mixture of both can be used. The coating weight of the metal electroplating layer before annealing can be adjusted by the current application time, etc. Note that the metal electroplated steel sheet before annealing means that the metal electroplating layer has not been subjected to an annealing process, and does not exclude forms in which a hot-rolled steel sheet before metal electroplating, a pickled sheet after hot rolling, or a cold-rolled steel sheet has been annealed in advance.

[0114] Here, the metal species of the electroplating layer are Cr, Mn, Fe, Co, Ni, Cu, Ga, Ge, As, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Os, Ir, Pt Although any of Au, Hg, Ti, Pb, and Bi can be used, Fe is more preferable, and therefore the manufacturing method for Fe-based electroplating is described below, however, the conditions for Fe-based electroplating described below can be similarly adopted for other metal-based electroplating.

[0115] The Fe ion content in the Fe-based electroplating bath before the start of current application is 2+ The content of Fe ions in the Fe-based electroplating bath is preferably 0.5 mol / L or more. 2+ A sufficient amount of Fe can be obtained if the Fe ion content in the Fe-based electroplating bath before the start of current application is 0.5 mol / L or more. In order to obtain a sufficient amount of Fe, the Fe ion content in the Fe-based electroplating bath before the start of current application is preferably 2.0 mol / L or less.

[0116] The Fe-based electroplating bath may contain Fe ions and at least one element selected from the group consisting of B, C, P, N, O, Ni, Mn, Mo, Zn, W, Pb, Sn, Cr, V, and Co. The total content of these elements in the Fe-based electroplating bath is preferably such that the total content of these elements in the Fe-based electroplating layer before annealing is 10 mass% or less. The metal elements may be contained as metal ions, and the nonmetal elements may be contained as part of boric acid, phosphoric acid, nitric acid, organic acid, etc. The iron sulfate plating solution may also contain a conductivity aid such as sodium sulfate or potassium sulfate, a chelating agent, or a pH buffer.

[0117] Other conditions for the Fe-based electroplating bath are not particularly limited. The temperature of the Fe-based electroplating solution is preferably 30°C or higher, and preferably 85°C or lower, in consideration of the ability to maintain a constant temperature. The pH of the Fe-based electroplating bath is not particularly specified, but is preferably 1.0 or higher in order to prevent a decrease in current efficiency due to hydrogen generation, and is preferably 3.0 or lower in consideration of the electrical conductivity of the Fe-based electroplating bath. The current density is 10 A / dm from the viewpoint of productivity. 2 From the viewpoint of easily controlling the deposition weight of the Fe-based electroplating layer, it is preferable to set the current to 150 A / dm or more. 2 The sheet threading speed is preferably 5 mpm or more from the viewpoint of productivity, and is preferably 150 mpm or less from the viewpoint of stably controlling the amount of adhesion.

[0118] As a treatment before the Fe-based electroplating treatment, a degreasing treatment and water washing for cleaning the steel sheet surface, and further, a pickling treatment and water washing for activating the steel sheet surface can be performed. Following these pretreatments, the Fe-based electroplating treatment is performed. The method of the degreasing treatment and water washing is not particularly limited, and a normal method can be used. In the pickling treatment, various acids such as sulfuric acid, hydrochloric acid, nitric acid, and mixtures thereof can be used. Among them, sulfuric acid, hydrochloric acid, or mixtures thereof are preferable. The concentration of the acid is not particularly specified, but considering the ability to remove the oxide film and the prevention of roughness (surface defects) due to excessive pickling, it is preferable to use about 1 to 20 mass%. In addition, the pickling treatment solution may contain an antifoaming agent, a pickling promoter, a pickling inhibitor, etc.

[0119] [Annealing process] Next, in one embodiment of the present invention, after the pickling step (after the cold rolling step if cold rolling is performed, after the metal plating (first plating) step if metal plating to form a metal plating layer (first plating layer) is performed, and after the metal plating (first plating) step if cold rolling and metal plating are performed), the steel sheet obtained as described above is annealed at an annealing temperature of (Ac1+0.4×(Ac3−Ac1))° C. or higher and 900° C. or lower for an annealing time of 20 seconds or longer. The number of annealing steps may be two or more, but is preferably one from the viewpoint of energy efficiency.

[0120] Annealing temperature: (Ac1+0.4×(Ac3-Ac1))℃ or higher and 900℃ or lower If the annealing temperature is less than (Ac1+0.4×(Ac3−Ac1))°C, the rate of austenite formation during heating in the two-phase region of ferrite and austenite becomes insufficient. As a result, the area ratio of ferrite increases excessively after annealing, and YS decreases. In addition, the C concentration in austenite during annealing increases excessively, and the desired λ and S are not obtained. Fmax Furthermore, it may be difficult to achieve a TS of 1180 MPa or more. On the other hand, when the annealing temperature exceeds 900°C, excessive grain growth of austenite occurs, and M SThe annealing point rises, a large amount of tempered martensite containing carbides is generated, it becomes difficult to obtain more than 3.0% retained austenite, and ductility decreases. Therefore, the annealing temperature is set to be (Ac1+0.4×(Ac3-Ac1))°C or more and 900°C or less. The annealing temperature is preferably 880°C or less. The annealing temperature is more preferably 870°C or less. In addition, the annealing temperature is preferably (Ac1+0.5×(Ac3-Ac1))°C or more, more preferably (Ac1+0.6×(Ac3-Ac1))°C or more. The annealing temperature is the maximum temperature reached in the annealing process.

[0121] The Ac1 point (℃) and the Ac3 point (℃) are calculated according to the following formula: Ac1 point (℃)=727.0-32.7×[%C]+14.9×[%Si]+2.0×[%Mn] Ac3 point (℃)=912.0-230×[%C]+31.6×[%Si]-20.4×[%Mn] Here, [%C] is the C content (% by mass), [%Si] is the Si content (% by mass), and [%Mn] is the Mn content (% by mass).

[0122] Annealing time: 20 seconds or more If the annealing time is less than 20 seconds, the austenite formation rate during heating in the ferrite-austenite two-phase region becomes insufficient, and as a result, the area ratio of ferrite increases excessively after annealing, lowering the YS. In addition, the C concentration in the austenite during annealing increases excessively, lowering the desired λ and S. Fmax cannot be achieved. Furthermore, it becomes difficult to achieve a TS of 1180 MPa or more. Therefore, the annealing time is set to 20 seconds or more. The annealing time is preferably 30 seconds or more, and more preferably 50 seconds or more. The upper limit of the annealing time is not particularly limited, but the annealing time is preferably 900 seconds or less, and more preferably 800 seconds or less. The annealing time is more preferably 300 seconds or less, and even more preferably 220 seconds or less. The annealing time is the holding time in the temperature range of (annealing temperature -40°C) or more and (annealing temperature) or less. In other words, the annealing time includes not only the holding time at the annealing temperature, but also the residence time in the temperature range of (annealing temperature -40°C) or more and (annealing temperature) or less during heating and cooling before and after reaching the annealing temperature.

[0123] Dew point of annealing atmosphere during annealing process: -30℃ or higher In one embodiment of the present invention, the dew point of the atmosphere in the annealing step (annealing atmosphere) is preferably -30°C. By performing annealing with the dew point of the annealing atmosphere in the annealing step being -30°C or higher, the decarburization reaction is promoted and the soft surface layer can be formed deeper. The dew point of the annealing atmosphere in the annealing step is more preferably -25°C or higher, even more preferably -15°C or higher, and most preferably higher than -5°C. Although there is no particular upper limit for the dew point of the annealing atmosphere in the annealing step, in order to suitably prevent oxidation of the surface of the Fe-based electroplating layer and to improve plating adhesion when a zinc plating layer is formed, it is preferable that the dew point of the annealing atmosphere in the annealing step is 30°C or less.

[0124] [First cooling process] Next, the steel sheet annealed as described above is cooled to a first cooling stop temperature of 400°C or higher and 600°C or lower.

[0125] First cooling stop temperature: 400℃ or more and 600℃ or less If the first cooling stop temperature is less than 400°C, the area fraction of bainitic ferrite increases excessively, the volume fraction of retained austenite exceeds a certain amount, and the desired λ and S are not obtained. Fmax On the other hand, if the first cooling stop temperature exceeds 600°C, the area ratio of pearlite increases, and strength may decrease. Therefore, the first cooling stop temperature is set to 400°C or more and 600°C or less. The first cooling stop temperature is preferably 460°C or more. In addition, the first cooling stop temperature is preferably 550°C or less.

[0126] [Holding process (suitable requirements)] After the first cooling step, if necessary, a holding step may be performed in which the steel sheet is held in a temperature range of 400° C. or more and 600° C. or less (hereinafter also referred to as a holding temperature range) for less than 80 seconds. Here, the holding temperature range may be the above-mentioned first cooling stop temperature.

[0127] Holding time in holding temperature range: Less than 80 seconds In the holding step, bainitic ferrite is generated, and C diffuses from the generated bainitic ferrite to the untransformed austenite adjacent to the bainitic ferrite, thereby ensuring a predetermined area ratio of retained austenite. Here, if the holding time in the holding temperature range is 80 seconds or more, the area ratio of bainitic ferrite increases excessively, and there is a risk of a decrease in YS. In addition, excessive diffusion of C from bainitic ferrite to untransformed austenite occurs, the area ratio of retained austenite exceeds 15.0%, and the desired λ and S are not obtained. Fmax may not be achieved. Therefore, the holding time in the holding temperature range is preferably less than 80 seconds. The holding time in the holding temperature range is more preferably less than 60 seconds. Note that the holding time in the holding temperature range does not include the residence time in the same temperature range after the zinc plating treatment in the plating step.

[0128] [Zinc plating process (second plating process)] After the first cooling step (or after the holding step, if a holding step is performed), the steel sheet may be subjected to a galvanizing treatment. By performing the galvanizing treatment, a galvanized steel sheet can be obtained. Examples of the galvanizing treatment include a hot-dip galvanizing treatment and a galvannealing treatment.

[0129] In the case of hot-dip galvanizing, it is preferable to immerse the steel sheet in a galvanizing bath at 440°C to 500°C, and then adjust the coating weight by gas wiping or the like. The hot-dip galvanizing bath is not particularly limited as long as it has the composition of the galvanized layer described above, but it is preferable to use a plating bath with an Al content of 0.10 mass% or more, with the balance being Zn and unavoidable impurities. The Al content is preferably 0.23 mass% or less.

[0130] In the case of galvannealing treatment, it is preferable to carry out alloying treatment by heating the galvanized steel sheet to an alloying temperature of 450° C. or higher after carrying out the hot-dip galvanizing treatment as described above. The above alloying temperature is preferably 600° C. or lower. If the alloying temperature is less than 450°C, the Zn-Fe alloying rate is slow, and alloying may be difficult. On the other hand, if the alloying temperature exceeds 600°C, untransformed austenite is transformed into pearlite, making it difficult to achieve a TS of 1180 MPa or more, and ductility is reduced. The alloying temperature is more preferably 470°C or more. Also, the alloying temperature is more preferably 570°C or less.

[0131] In addition, the coating weight of both hot-dip galvanized steel sheet (GI) and galvannealed steel sheet (GA) is 20 g / m per side. 2 The coating weight of the zinc-plated layer on one side is preferably 80 g / m or more. 2 It is preferable that the plating thickness is set to be equal to or less than 100 nm. The plating thickness can be adjusted by gas wiping or the like.

[0132] [Second cooling process] Next, the steel sheet after the first cooling step is cooled to a second cooling stop temperature of 100°C or higher and 300°C or lower at an average cooling rate of 25.0°C / sec or lower.

[0133] Second cooling stop temperature: 100℃ or more and 300℃ or less The second cooling step is a step necessary for controlling the area ratio of tempered martensite and the area ratio of retained austenite generated in the subsequent reheating step within a predetermined range. Here, if the second cooling stop temperature is less than 100°C, the untransformed austenite present in the steel in the second cooling step is almost entirely transformed into martensite. As a result, the area ratio of tempered martensite ultimately increases excessively, making it difficult to obtain retained austenite of more than 3.0%, and ductility decreases. On the other hand, if the second cooling stop temperature exceeds 300°C, the area ratio of tempered martensite decreases and the area ratio of fresh martensite increases. In addition, the amount of diffusible hydrogen in the steel sheet may also increase. As a result, the desired λ and S Fmax In addition, the desired α may not be obtained. Therefore, the second cooling stop temperature is set to 100°C or higher and 300°C or lower. The second cooling stop temperature is preferably 120°C or higher. In addition, the first cooling stop temperature is preferably 280°C or lower.

[0134] Average cooling rate in the second cooling process: 25.0℃ / sec or less If the cooling rate in the second cooling step exceeds 25.0°C / sec, fine carbides are formed and the density of the carbides in the tempered martensite becomes equal to or greater than a predetermined value. As a result, the desired λ and S Fmax In addition, the desired α may not be obtained. Therefore, the average cooling rate in the second cooling step is set to 25.0° C. / sec or less. Here, the average cooling rate can be calculated by "(cooling start temperature (°C) - second cooling stop temperature (°C))" / cooling time (s)".

[0135] In the present invention, when the steel plate is cooled to the second cooling stop temperature, the strain is 2.0 kgf / mm in the temperature range of 300°C to 450°C. 2 The above tension is applied one or more times. Then, the steel sheet after being applied with the above tension is subjected to a process of applying the tension four or more times while being brought into contact with a roll having a diameter of 500 mm or more and 1500 mm or less for 1 / 4 of the roll circumference per pass, and a process of applying the tension two or more times while being brought into contact with a roll having a diameter of 500 mm or more and 1500 mm or less for 1 / 2 of the roll circumference per pass. As mentioned above, the load on the steel plate is 2.0 kgf / mm 2 By applying the above tension at least once and for the specified number of passes, the residual austenite that is excessively formed in the steel sheet structure undergoes deformation-induced transformation to martensite, and further to tempered martensite during the subsequent cooling. As a result, the desired λ and S Fmax You can get.

[0136] The number of passes imparted to the steel sheet while being in contact with the roll for 1 / 4 revolution is preferably 5 passes or more, and more preferably 6 passes or more. Although there is no particular upper limit, the number of passes imparted to the steel sheet while being in contact with the roll for 1 / 4 revolution is preferably 12 passes or less, and more preferably 10 passes or less. The number of passes imparted to the steel sheet while being in contact with the roll for 1 / 2 revolution is preferably 3 passes or more, and more preferably 4 passes or more. Although there is no particular upper limit, the number of passes imparted to the steel sheet while being in contact with the roll for 1 / 2 revolution is preferably 6 passes or less, and more preferably 5 passes or less.

[0137] Here, the tension is calculated by multiplying the total load (kgf) of the load cells on the left and right sides of the roll by the cross-sectional area of ​​the steel plate (= plate thickness (mm) × plate width (mm)) (mm 2 The load cell must be placed parallel to the tension direction. Here, the load cells are preferably disposed 200 mm from both ends of the roll. The length of the roll used is preferably 1500 mm or more. The length of the roll used is preferably 2500 mm or less. The tension is preferably 2.2 kgf / mm 2More preferably, it is 2.4 kgf / mm 2 That's all. The tension is preferably 15.0 kgf / mm 2 More preferably, it is 10.0 kgf / mm 2 This tension is more preferably 7.0 kgf / mm 2 and even more preferably 4.0 kgf / mm 2 The following is the result.

[0138] In addition, when applying tension more than once, for example, applying tension twice means first applying 2.0 kgf / mm 2 The above tension is applied once, and then the tension is increased to 2.0 kgf / mm 2 After it becomes less than 2.0kgf / mm 2 The tension applied three times means that the first tension is 2.0 kgf / mm 2 The above tension is applied once, and then the tension is increased to 2.0 kgf / mm 2 After it becomes less than 2.0kgf / mm 2 A tension of 2.0kgf / mm or more is applied, and then the tension is increased to 2.0kgf / mm 2 After it becomes less than 2.0kgf / mm for the third time 2 This means that a tension of at least this level is applied.

[0139] [Reheating process] Next, the steel sheet is reheated to a temperature range of more than 300°C and not more than 500°C (hereinafter also referred to as a reheating temperature range), and the steel sheet is held in the temperature range of more than 300°C and not more than 500°C for 20 seconds to 900 seconds. This tempers the martensite present in the steel at the end of the second cooling step, and also causes the carbon that is supersaturated in the martensite to diffuse into the untransformed austenite, forming austenite that is stable at room temperature, i.e., retained austenite.

[0140] Reheating temperature (tempering temperature): Over 300℃ and below 500℃ If the reheating temperature (tempering temperature) is 300°C or lower, the tempering of the martensite present in the steel at the end of the second cooling process does not proceed sufficiently, and the amount of fresh martensite increases excessively. In addition, the coarsening of the carbides in the tempered martensite does not proceed sufficiently, and the density of the carbides in the tempered martensite becomes a predetermined amount or more. As a result, the desired λ, α and S Fmax Furthermore, the hydrogen contained in the base steel sheet is not sufficiently released to the outside, and the amount of diffusible hydrogen in the base steel sheet increases, which further reduces the hole expandability and bendability. On the other hand, if the reheating temperature (tempering temperature) exceeds 500°C, the tempering of martensite present in the steel at the end of the second cooling process proceeds excessively, making it difficult to achieve a TS of 1180MPa or more. In addition, the untransformed austenite present in the steel at the end of the second cooling process decomposes as carbide (pearlite), resulting in a decrease in ductility. Furthermore, the external release of hydrogen contained in the base steel sheet may become insufficient, increasing the amount of diffusible hydrogen in the base steel sheet. This results in a decrease in hole expandability. Therefore, the reheating temperature is set to be more than 300°C and not more than 500°C. The reheating temperature is the maximum temperature reached in the reheating process. The reheating temperature is preferably 340°C or more, more preferably 360°C or more. The reheating temperature is preferably 460°C or less, more preferably 440°C or less.

[0141] Holding time in the reheating temperature range (tempering time): 20 seconds or more and 900 seconds or less If the holding time (tempering time) in the reheating temperature range is less than 20 seconds, the martensite present in the steel at the end of the second cooling step does not temper sufficiently, and fresh martensite increases excessively. Also, the coarsening of carbides in the tempered martensite does not proceed sufficiently, and the density of carbides in the tempered martensite may exceed a predetermined value. As a result, the desired λ, α and S Fmax Furthermore, the hydrogen contained in the base steel sheet is not sufficiently released to the outside, and the amount of diffusible hydrogen in the base steel sheet increases, which further reduces the hole expandability and bendability. On the other hand, if the holding time (tempering time) in the reheating temperature range exceeds 900 seconds, the tempering of the martensite present in the steel at the end of the second cooling step proceeds excessively, making it difficult to achieve a TS of 1180 MPa or more. In addition, the untransformed austenite present in the steel at the end of the second cooling step decomposes as carbide (pearlite), resulting in a decrease in ductility. Therefore, the holding time in the reheating temperature range is set to 20 seconds or more and 900 seconds or less. The holding time is preferably 30 seconds or more, more preferably 40 seconds or more. The holding time is preferably 500 seconds or less, more preferably 100 seconds or less. The holding time in the reheating temperature range includes not only the holding time at the reheating temperature, but also the residence time in that temperature range during heating and cooling before and after reaching the reheating temperature.

[0142] Carbide control parameter CP during reheating: 10,000 to 15,000 When the carbide control parameter CP during reheating is less than 10,000, the tempering of the martensite present in the steel at the end of the second cooling process does not proceed sufficiently, and the amount of fresh martensite increases excessively. In addition, the coarsening of the carbides in the tempered martensite does not proceed sufficiently, and the density of the carbides in the tempered martensite becomes equal to or greater than a predetermined amount. As a result, the desired λ, α and S Fmax Furthermore, the hydrogen contained in the base steel sheet is not sufficiently released to the outside, and the amount of diffusible hydrogen in the base steel sheet increases, which further deteriorates the hole expandability and bendability. On the other hand, if the carbide control parameter CP during reheating exceeds 15,000, the tempering of martensite present in the steel at the end of the second cooling process proceeds excessively, making it difficult to achieve a TS of 1,180 MPa or more. In addition, the untransformed austenite present in the steel at the end of the second cooling process decomposes as carbides (pearlite), resulting in a decrease in ductility. Therefore, the carbide control parameter CP during reheating is set to 10,000 or more and 15,000 or less. The carbide control parameter CP during reheating is preferably 11000 or more, and more preferably 12000 or more. The carbide control parameter CP during reheating is preferably 14500 or less, and more preferably 14000 or less.

[0143] The carbide control parameters during reheating are calculated using the following formula: CP=(T+273)×(k+1.2×logt)...Equation (1) Here, CP is the carbide control parameter, T is the tempering temperature (℃), k is a material constant dependent on the C content, and t is the tempering time (sec). The 1.2 in the term 1.2 × log t is a correction coefficient (predetermined correction coefficient) that takes into account the cooling time after the reheating process. The material constant k is calculated by the following formula: k = -6 × C M +17.8 Here, C M is the carbon content (mass%) in the martensite formed in the second cooling step. The carbon content in the martensite formed in the second cooling step can be measured as follows. First, the carbon amount in each phase immediately before the second cooling step satisfies the following relationship. V γ1 ×C γ1 +V F ×C F +V BF ×C BF =C T ...Equation (2) V γ1 =1 - V F -V BF ...Equation (3) Here, V γ1 , C γ1 is the area ratio (%) of untransformed austenite immediately before the second cooling step and the carbon concentration (mass%) in the untransformed austenite, V F , C F is the area ratio (%) of ferrite and the carbon concentration (mass%) in the ferrite immediately before the second cooling step, V BF , C BFis the area ratio (%) of bainitic ferrite and the carbon concentration (mass%) in the bainitic ferrite immediately before the second cooling step, C T is the carbon concentration (mass%) in the steel (just before the second cooling step). Furthermore, the area ratio of ferrite just before the second cooling process V F (%) and the area fraction of bainitic ferrite V BF The carbon concentration C (%) in the ferrite can be considered to be equivalent to the area ratio (%) of ferrite and the area ratio (%) of bainitic ferrite in the final structure (the steel structure of the steel sheet obtained at the end). F (mass%) and carbon concentration in bainitic ferrite C BF (% by mass) can be set to zero. Therefore, equation (2) becomes: C T =V γ1 ×C γ1 +V F ×0(zero)+V BF ×0(zero)=V γ1 ×C γ1 ···Formula (2-2) It becomes. In addition, from equation (2-2) and equation (3), C T =(1-V F -V BF )×C γ1 Therefore, C γ1 =C T / (1-V F -V BF Furthermore, the transformation from γ1 (untransformed austenite) to martensite in the second cooling step is a transformation that does not involve the diffusion of C, so M =C γ1 That is, C M =C γ1 =C T / (1-V F -V BF ).

[0144] The cooling conditions after holding in the reheating temperature range are not particularly limited and may be in accordance with a conventional method. For example, gas jet cooling, mist cooling, roll cooling, water cooling, and air cooling may be used as the cooling method. In addition, from the viewpoint of preventing oxidation of the surface, it is preferable to cool to 50°C or less after holding in the reheating temperature range, and more preferably to about room temperature. The average cooling rate in the cooling after holding in the reheating temperature range is preferably, for example, 1°C / sec or more and 50°C / sec or less.

[0145] The steel sheet obtained as described above may be further subjected to temper rolling. If the reduction rate of temper rolling exceeds 2.00%, the yield stress increases, and the dimensional accuracy may decrease when the steel sheet is formed into a member. Therefore, the reduction rate of temper rolling is preferably 2.00% or less. The lower limit of the reduction rate of temper rolling is not particularly limited, but is preferably 0.05% or more from the viewpoint of productivity. The temper rolling may be performed on an apparatus continuous with the annealing apparatus for performing each of the above-mentioned steps (online), or may be performed on an apparatus discontinuous with the annealing apparatus for performing each of the steps (offline). The number of rolling times of temper rolling may be one or two or more. As long as the same elongation rate as that of temper rolling can be imparted, rolling using a leveler or the like may be used.

[0146] The other conditions than those mentioned above are not particularly limited, and may be those according to conventional methods.

[0147] [3. Materials] Next, a member according to one embodiment of the present invention will be described. A member according to one embodiment of the present invention is a member made using the above-mentioned steel plate (as a raw material). For example, the raw material steel plate is subjected to at least one of forming and joining to form a member. Here, the above steel plate has a TS of 1180 MPa or more, a high YS, excellent press formability (ductility, hole expandability, and bendability), and fracture resistance properties during crushing (bending fracture properties and axial crush properties). Therefore, the member according to one embodiment of the present invention has high strength and excellent impact resistance properties. Therefore, the member according to one embodiment of the present invention is particularly suitable for application to impact energy absorbing members used in the automotive field.

[0148] [4. Manufacturing methods for components] Next, a method for manufacturing a member according to one embodiment of the present invention will be described. A method for manufacturing a component according to one embodiment of the present invention includes a step of subjecting the above-mentioned steel plate (e.g., a steel plate manufactured by the above-mentioned steel plate manufacturing method) to at least one of forming and joining to form a component. Here, the molding method is not particularly limited, and for example, a general processing method such as press processing can be used. The joining method is also not particularly limited, and for example, general welding such as spot welding, laser welding, and arc welding, rivet joining, crimp joining, etc. The molding conditions and joining conditions are not particularly limited, and may be in accordance with ordinary methods. EXAMPLES

[0149] Steel materials having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) were melted in a converter and made into steel slabs by a continuous casting method. In Table 1, "-" indicates the content of unavoidable impurities. The calculated transformation points Ac1 (℃) and Ac3 (℃) shown in Table 1 are calculated using the following formula. Ac1 point (℃)=727.0-32.7×[%C]+14.9×[%Si]+2.0×[%Mn] Ac3 point (℃)=912.0-230×[%C]+31.6×[%Si]-20.4×[%Mn] Here, [%C] is the C content (% by mass), [%Si] is the Si content (% by mass), and [%Mn] is the Mn content (% by mass).

[0150] The obtained steel slab was heated to 1200°C, and after heating, the steel slab was subjected to hot rolling consisting of rough rolling and finish rolling at a finish rolling temperature of 900°C to obtain hot rolled steel sheets. Next, No. 1 to No. 61, No. 64 to No. 78, No. 84 to No. 98, and No. 104 to No. 109 of the obtained hot rolled steel sheets were subjected to pickling and cold rolling (reduction rate: 50%) to obtain cold rolled steel sheets having the thicknesses shown in Tables 3, 6, and 9. In addition, No. 62 to No. 63, No. 79 to No. 83, and No. 99 to No. 103 of the obtained hot rolled steel sheets were subjected to pickling to obtain hot rolled steel sheets (white skin) having the thicknesses shown in Tables 3, 6, and 9. Next, the obtained cold-rolled steel sheet or hot-rolled steel sheet (white skin) was subjected to the annealing process, the first cooling process, the holding process, the galvanizing process, the second cooling process and the reheating process under the conditions shown in Table 2, and also to the first plating process (metal plating process), the annealing process, the first cooling process, the holding process, the second plating process (galvanizing process), the second cooling process and the reheating process under the conditions shown in Tables 5 and 8, to obtain a steel sheet (galvanized steel sheet). Tables 5 and 8 show whether or not the first plating process (metal plating process) was performed for steel sheets No. 64 to No. 109, and the type of plating performed in the metal plating process. Tables 6 and 9 show the thickness of the soft surface layer, the amount of metal plating applied, and the hardness distribution of the soft surface layer for steel sheets No. 64 to No. 109.

[0151] Here, in the galvanizing process, a hot-dip galvanizing treatment or a galvannealed treatment was performed to obtain a hot-dip galvanized steel sheet (hereinafter also referred to as GI) or an alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA). In Tables 2, 5, and 8, the type of plating process is also indicated as "GI" and "GA". In the case of GI steel sheets in Tables 2, 5, and 8, no alloying treatment was performed, so the alloying temperature is indicated as -. In Table 8, cold-rolled steel sheets obtained without performing galvanizing treatment in the galvanizing process are indicated as "CR", and hot-rolled steel sheets obtained without performing galvanizing treatment in the galvanizing process are indicated as "HR".

[0152] The galvanizing bath temperature was 470°C for both GI and GA production. When manufacturing GI, the amount of zinc plating is 45 to 72 g / m per side. 2 When manufacturing GA, the thickness is 45 g / m per side. 2 It was decided. The composition of the zinc plating layer of the finally obtained zinc-plated steel sheet was as follows: GI: 0.1-1.0 mass% Fe, 0.2-0.33 mass% Al, and the balance was Zn and unavoidable impurities, while GA: 8.0-12.0 mass% Fe, 0.1-0.23 mass% Al, and the balance was Zn and unavoidable impurities. In addition, the zinc plating layers were formed on both sides of the base steel sheet in each case.

[0153] In Tables 2, 5, and 8, pass number 1 is 2.0 kgf / mm in the temperature range of 300°C to 450°C during the second cooling process. 2 number of passes is the number of passes in which an average tension of at least 100 mm or more is applied to the steel sheet while it is in contact with a roll having a diameter of at least 500 mm and at most 1500 mm for 1 / 4 revolution of the roll per pass, and number of passes 2 is the number of passes in which the steel sheet is then in contact with a roll having a diameter of at least 500 mm and at most 1500 mm for 1 / 2 revolution of the roll per pass.

[0154] Using the obtained steel sheets, the steel structure of the base steel sheets was identified and the amount of diffusible hydrogen was measured in the manner described above. The measurement results are shown in Tables 3, 6, and 9. In Tables 3, 6, and 9, BF ​​is bainitic ferrite, TM is tempered martensite, RA is retained austenite, FM is fresh martensite, LB is lower bainite, P is pearlite, and θ is carbide. In addition, C M is the carbon content in the martensite formed in the second cooling process, C γ is the carbon content in the retained austenite, ρ C is the density of carbides in the tempered martensite.

[0155] The method for measuring the surface soft layer is as follows. After smoothing the thickness cross section (L cross section) parallel to the rolling direction of the steel plate by wet polishing, measurements were taken at 1 μm intervals from a position 1 μm from the steel plate surface in the thickness direction to a position 100 μm in the thickness direction using a Vickers hardness tester based on JIS Z 2244-1 (2020) with a load of 10 gf. Measurements were then taken at 20 μm intervals up to the center of the plate thickness. The region where the hardness has decreased to 85% or less compared to the hardness at the 1 / 4 position of the plate thickness is defined as the soft layer (surface soft layer), and the thickness in the thickness direction of the region is defined as the thickness of the soft layer.

[0156] In addition, tensile tests, hole expansion tests, VDA bending tests, V-VDA bending tests, and axial crush tests were performed according to the following procedures, and the tensile strength (TS), yield stress (YS), total elongation (El), limit hole expansion ratio (λ), limit bending angle (α) in the VDA bending test, and stroke at maximum load in the V-VDA bending test (S Fmax ) and the presence or absence of axial compression fracture were evaluated.

[0157] ·TS 〇(Pass): 1180MPa or more × (Fail): Less than 1180MPa

[0158] YS 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 750MPa≦YS (B) When TS is 1320MPa or less, YS is 850MPa or less ×(Fail): (A) When 1180MPa≦TS<1320MPa, 750MPa>YS (B) When 1320MPa≦TS, 850MPa>YS

[0159] ·El 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 12.0%≦El (B) When TS is 1320MPa or less, 10.0% or less El ×(Fail): (A) When 1180MPa≦TS<1320MPa, 12.0%>El (B) When 1320MPa≦TS, 10.0%>El

[0160] λ 〇(Pass): 30% or more × (Fail): Less than 30%

[0161] α 〇(Pass): 80° or more × (Fail): Less than 80°

[0162] ·S Fmax 〇 (pass): 26.0mm or more × (Fail): Less than 26.0 mm

[0163] - Presence or absence of axial compression fracture A (Pass): No cracks were observed in the sample after the axial crush test. B (Pass): Two or fewer cracks were observed on the sample after the axial crush test. C (Pass): Three or fewer cracks were observed on the sample after the axial crush test. D (Fail): Four or more cracks were observed on the sample after the axial crush test, or the sample broke after the axial crush test.

[0164] (1) Tensile test The tensile test was performed in accordance with JIS Z 2241 (2011). That is, JIS No. 5 test pieces were taken from the obtained steel sheets so that the longitudinal direction was perpendicular to the rolling direction of the base steel sheet. Using the taken test pieces, tensile tests were performed at a crosshead speed of 10 mm / min, and TS, YS, and El were measured. The results are shown in Tables 4, 7, and 10.

[0165] (2) Hole expansion test The hole expansion test was performed in accordance with JIS Z 2256 (2020). That is, a test piece of 100 mm × 100 mm was taken from the obtained steel plate by shear processing. A hole of 10 mm in diameter was punched in the test piece with a clearance of 12.5%. Next, a wrinkle holding force of 9 ton (88.26 kN) was applied around the hole using a die with an inner diameter of 75 mm, and a conical punch with an apex angle of 60 ° was pressed into the hole, and the diameter of the hole of the test piece at the crack occurrence limit (when cracks occurred) was measured. Then, the limit hole expansion ratio: λ (%) was calculated by the following formula. In addition, λ is an index for evaluating the stretch flangeability. The results are shown in Tables 4, 7, and 10. λ(%)={(D f -D0) / D0}×100 Where: D f : diameter of the hole in the test piece when the crack occurred (mm) D0: Initial diameter of the hole in the test piece (mm) It is.

[0166] (3) VDA bending test The VDA bending test was performed in accordance with the VDA standard (VDA238-100) prescribed by the German Association of the Automotive Industry. Specifically, a test piece of 70 mm × 60 mm was taken from the obtained steel plate by shearing, where the 60 mm side was parallel to the rolling (L) direction. The test piece was subjected to a VDA bending test under the following conditions. Test method: Roll support, punch intrusion Roll diameter: φ30mm Punch tip R: 0.4 mm Distance between rolls: (sheet thickness x 2) + 0.5 mm Stroke speed: 20mm / min Bending direction: perpendicular to rolling (C) direction At this time, the angle of the outer bend of the center of the plate-shaped test piece when the load F from the pushing bending jig from above is maximum is measured as the limit bending angle (°). The average value of the limit bending angle at the maximum load when the above VDA bending test is performed three times is taken as α (°). The results are shown in Tables 4, 7, and 10.

[0167] (4) V-VDA bending test (V bending + orthogonal VDA bending test) The V-VDA bending test was carried out as follows. From the obtained steel plate, a 60 mm × 65 mm test piece was taken by shearing. Here, the 60 mm side is parallel to the rolling (L) direction. The test piece was prepared by bending the steel plate 90° (primary bending) in the rolling (L) direction with the width (C) direction as the axis at a curvature radius / plate thickness of 4.2. In the 90° bending (primary bending), as shown in Figure 2-1 (a), a punch B1 was pressed into the steel plate placed on a die A1 having a V groove to obtain a test piece T1. Next, as shown in Figure 2-1 (b), a punch B2 was pressed into the test piece T1 placed on a support roll A2 so that the bending direction was perpendicular to the rolling direction, and an orthogonal bending (secondary bending) was performed. In Figures 2-1 (a) and 2-1 (b), the symbol D1 indicates the width (C) direction, and the symbol D2 indicates the rolling (L) direction. The V-bending conditions in the V-VDA bending test (V bending + orthogonal VDA bending test) are as follows: Test method: Die support, punch push Molding load: 10t Test speed: 30mm / min Holding time: 5s Bending direction: Rolling (L) direction The VDA bending conditions in the V-VDA bending test are as follows: Test method: Roll support, punch intrusion Roll diameter: φ30mm Punch tip R: 0.4 mm Distance between rolls: (sheet thickness x 2) + 0.5 mm Stroke speed: 20mm / min Test piece size: 60mm x 60mm Bending direction: perpendicular to rolling (C) direction In the stroke-load curve obtained when performing the above VDA bending, the stroke at the maximum load is obtained. The average value of the stroke at the maximum load when the above V-VDA bending test is performed three times is S Fmax The results are shown in Tables 4, 7, and 10.

[0168] (5) Axial crush test A 160 mm x 200 mm test piece was taken from the obtained steel plate by shearing. Here, the 160 mm side is parallel to the rolling (L) direction. Using a die having a punch shoulder radius of 5.0 mm and a die shoulder radius of 5.0 mm, the hat-shaped member 10 shown in Fig. 6-1(a) and Fig. 6-1(b) was produced by forming (bending) to a depth of 40 mm. In addition, the steel plate used as the material for the hat-shaped member was separately cut into a size of 80 mm x 200 mm. Next, the cut-out steel plate 20 and the hat-shaped member 10 were spot-welded to produce a test member 30 as shown in Fig. 6-1(a) and Fig. 6-1(b). Fig. 6-1(a) is a front view of the test member 30 produced by spot-welding the hat-shaped member 10 and the steel plate 20. Fig. 6-1(b) is a perspective view of the test member 30. The position of the spot welded portion 40 was such that the end of the steel plate and the welded portion were spaced 10 mm apart, and the distance between the welded portions was 45 mm, as shown in FIG. 6-1(b). Next, as shown in FIG. 6-2(c), the test member 30 was joined to the base plate 50 by TIG welding to prepare a sample for the axial crush test. Next, the impactor 60 was made to collide with the prepared sample for the axial crush test at a constant velocity of 10 mm / min, and the sample for the axial crush test was crushed by 70 mm. As shown in FIG. 6-2(c), the crush direction D3 was parallel to the longitudinal direction of the test member 30. The samples after crushing were evaluated in the manner described above, and the results are shown in Tables 4, 7, and 10.

[0169] In the VDA bending test, V-VDA bending test and axial crush test of steel plates with a thickness of over 1.2 mm, the effect of plate thickness was taken into consideration and all tests were conducted with steel plates with a thickness of 1.2 mm. Steel plates with a thickness of over 1.2 mm were ground on one side to make the plate thickness 1.2 mm. Since there is a concern that the grinding process may affect the bendability of the steel plate surface, the ground surface was placed on the inside of the bend (the side that comes into contact with the punch) in the VDA bending test, and in the V-VDA bending test, the ground surface was placed on the outside of the bend (the side that comes into contact with the die) during the V-bend test, and then the ground surface was placed on the inside of the bend (the side that comes into contact with the punch) for the VDA bending test. On the other hand, in the VDA bending test, V-VDA bending test and axial crush test of steel plates with a thickness of 1.2 mm or less, the effect of the plate thickness was small, so the tests were performed without grinding.

[0170] Furthermore, "*1" and "*2" in Tables 4, 7, and 10 respectively indicate the length of cracks formed at the V-bend ridge and the L-section of the VDA bend ridge when a V-VDA bend test was performed up to the maximum load point, and the change in the grain size of bainitic ferrite in the plate thickness direction before and after processing in a region 50 μm from the steel plate surface on the outer side of the VDA bend and 50 μm to the left and right of the apex of the VDA bend (the region formed from each position of the start line that exists from the apex of the VDA bend on the outer side of the VDA bend to a position 50 μm in the plate thickness direction, up to 50 μm on each side of the start line in the vertical direction).

[0171] <Nano hardness measurement> In order to obtain excellent bendability during press forming and excellent bending fracture properties during collision, when the nanohardness is measured at 300 or more points in a 50μm×50μm region on the sheet surface at 1 / 4 and 1 / 2 positions in the sheet thickness direction from the surface layer of the base steel sheet, it is more preferable that the number of measurements of nanohardness of 7.0GPa or more at 1 / 4 positions in the sheet thickness direction from the surface of the soft surface layer is 0.10 or less relative to the total number of measurements at 1 / 4 positions in the sheet thickness direction. If the ratio of nanohardness of 7.0GPa or more is 0.10 or less, it means that the ratio of hard structures (martensite, etc.), inclusions, etc. is small, so it is possible to further suppress the generation and connection of voids and the development of cracks in hard structures (martensite, etc.) and inclusions during press forming and collision, and excellent R / t and SFmax are obtained.

[0172] In the case of zinc plating, after peeling off the plating layer, the steel sheet was mechanically polished from the surface to 1 / 4 of the way down to the soft surface layer at 5μm, then buffed with diamond and alumina from the surface to 1 / 4 of the way down to the soft surface layer, and then polished with colloidal silica. Using a Hysitron Tribo-950, a Berkovich-shaped diamond indenter was used. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions. The plating layer to be peeled off is the zinc plating layer when a zinc plating layer is formed, the metal plating layer when a metal plating layer is formed, and the zinc plating layer and the metal plating layer when a zinc plating layer and a metal plating layer are formed.

[0173] Next, the surface soft layer was mechanically polished to a position halfway down the thickness direction, buffed with diamond and alumina, and polished with colloidal silica. Load: 500μN Measurement area: 50μm x 50μm Dot spacing: 2μm A total of 512 nano-hardness points were measured under the above conditions.

[0174] [Table 1-1]

[0175] [Table 1-2]

[0176] [Table 2-1]

[0177] [Table 2-2]

[0178] [Table 3-1]

[0179] [Table 3-2]

[0180] [Table 4-1]

[0181] [Table 4-2]

[0182] [Table 5]

[0183] [Table 6]

[0184] [Table 7]

[0185] [Table 8]

[0186] [Table 9]

[0187] [Table 10]

[0188] In Tables 1 to 10, the underlined parts indicate values ​​outside the appropriate range of the present invention. As shown in Tables 4, 7, and 10, the tensile strength (TS), yield stress (YS), total elongation (El), limit hole expansion ratio (λ), limit bending angle (α) in the VDA bending test, stroke at maximum load in the V-VDA bending test (S Fmax ) passed the axial crush test, and no fractures occurred in the test. On the other hand, in the comparative example, the tensile strength (TS), yield stress (YS), total elongation (El), limit hole expansion ratio (λ), limit bending angle (α) in the VDA bending test, stroke at maximum load in the V-VDA bending test (S Fmax ) and at least one of the fracture occurrences in the axial crush test was insufficient. In Tables 5 to 10, when the dew point was in the range of -30°C or higher and -5°C or lower, the soft layer thickness was less than 11 μm, and the fracture (visual cracking) in the axial crushing test was rated as "B" or "C". However, even when the soft layer thickness was less than 11 μm, if a metal plating layer was present, the fracture (visual cracking) in the axial crushing test was rated as "A".

[0189] In addition, the steel plate according to the present invention was used to form and join components, which have tensile strength (TS), yield stress (YS), total elongation (El), limit hole expansion ratio (λ), limit bending angle (α) in the VDA bending test, and stroke at maximum load in the V-VDA bending test (S Fmax ) had the excellent properties characteristic of the present invention, and none of them broke in the axial crushing test, showing that they had the excellent properties characteristic of the present invention. [Explanation of symbols]

[0190] 10 Hat-shaped member 20. Galvanized steel sheet 30 Test components 40 Spot welds 50 Main plate 60 Impactor A1 Die A2 Support roll B1 Punch B2 Punch D1 width (C) direction D2 Rolling (L) direction D3 Crushing direction D4 Thickness direction T1 test piece T2 specimen P Maximum load point R The region where the stroke is increased from the maximum load point and the load is 94.9 to 99.9% of the maximum load. AB: At the L cross section in the overlapping region of the V-bend ridgeline and the VDA-bend ridgeline, the area is 0 to 50 μm from the steel sheet surface on the outside of the VDA bend, and 50 μm to the left and right of the apex of the VDA bend. L section in the overlapping region of the AL V-bend ridge and the VDA-bend ridge F Ferrite BF Bainitic ferrite BF1 Bainitic ferrite before deformation Bainitic ferrite after BF2 deformation TM Tempered martensite θ Carbide H1 Hard second phase X1 Island second phase

Claims

1. A steel sheet comprising a base steel sheet or comprising the base steel sheet and a zinc-plated layer and / or a metal-plated layer, The base steel sheet is In mass percent, C: 0.050% or more and 0.332% or less, Si: more than 0.75% and less than 3.00%, Mn: 2.00% or more and less than 3.50%; P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% or more and 2.000% or less; N: 0.0100% or less The balance is Fe and unavoidable impurities, The base steel sheet is Area ratio of bainitic ferrite: 3.0% or more and 20.0% or less, Area ratio of tempered martensite: 40.0% or more and 90.0% or less, Area ratio of retained austenite: 3.8% or more and 15.0% or less, Carbon concentration in retained austenite: 0.60 mass% or more and 1.30 mass% or less, Area ratio of fresh martensite: 10.0% or less, Density of carbides in tempered martensite: 8.0 pieces / μm 2 below, a remaining structure other than bainitic ferrite, tempered martensite, retained austenite, and fresh martensite is one or more selected from ferrite, lower bainite, pearlite, and carbide, an area ratio of the remaining structure: 27.8% or less, an area ratio of the pearlite: 5.0% or less, and The base steel sheet has a diffusible hydrogen content of 0.50 ppm by mass or less, Furthermore, a V-VDA bending test was performed up to the maximum load point. In the L section, The length of the crack is 400 μm or less, Furthermore, in the region formed at a position up to 50 μm on each side of the start line in the vertical direction from each position of the start line that exists from the outer bend apex of the VDA bend as the starting point to a position of 50 μm in the plate thickness direction, With respect to the average grain size of bainitic ferrite in the sheet thickness direction, the ratio of the average grain size before processing to the average grain size after processing is 5.0 or less; The tensile strength is 1180 MPa or more, Further optionally, the steel plate satisfies one or more of the following (A), (B) and (C): (A) The steel sheet has a zinc-plated layer as the outermost layer on one or both sides. (B) When the base steel sheet has a surface layer in a region of 200 μm or less from the surface of the base steel sheet in the sheet thickness direction, The surface layer has a surface soft layer having a Vickers hardness of 85% or less of the Vickers hardness at a quarter of the plate thickness position, When the nano hardness was measured at 300 or more points in a 50 μm×50 μm region on the sheet surface at a 1 / 4 position and a 1 / 2 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet, the ratio of the number of measurements of nano hardness of 7.0 GPa or more on the sheet surface at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet to the total number of measurements at a 1 / 4 position of the sheet thickness direction depth of the soft surface layer is 0.10 or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position of ¼ of the sheet thickness direction depth of the soft surface layer from the surface of the base steel sheet is 1.8 GPa or less, Furthermore, the standard deviation σ of the nano-hardness of the sheet surface at a position half the depth in the sheet thickness direction of the soft surface layer from the surface of the base steel sheet is 2.2 GPa or less. (C) The steel sheet has a metal plating layer formed on one or both sides of the base steel sheet.

2. The composition of the base steel sheet further comprises, in mass%, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less; REM: 0.0200% or less The steel sheet according to claim 1, comprising at least one selected from the following:

3. A member made using the steel sheet according to claim 1 or 2.

4. A hot rolling process in which a steel slab having the composition according to claim 1 or 2 is hot rolled to obtain a hot rolled steel sheet; A pickling process for pickling the hot-rolled steel sheet; The steel sheet after the pickling process is subjected to annealing at a temperature of: (Ac 1 + 0.4 × (Ac 3 -Ac 1 )) ° C. or higher and 900 ° C. or lower, and annealing for 20 seconds or more; and A first cooling step of cooling the steel sheet after the annealing step to a first cooling stop temperature of 400°C or more and 600°C or less; The steel sheet after the first cooling step is cooled to a second cooling stop temperature of 100° C. or more and 300° C. or less at an average cooling rate of 25.0° C. / sec or less, During the cooling, the steel plate is subjected to a pressure of 2.0 kgf / mm in a temperature range of 300°C to 450°C. 2 Apply the above tension at least once, after that, A treatment in which the steel sheet is subjected to four or more passes while being brought into contact with a roll having a diameter of 500 mm or more and 1500 mm or less for one pass for a quarter of a circumference of the roll; and A second cooling process in which the steel sheet is subjected to two or more passes while being brought into contact with a roll having a diameter of 500 mm or more and 1500 mm or less for 1 / 2 rotation of the roll per pass; a reheating process in which the steel sheet after the second cooling process is heated to a tempering temperature in a temperature range of more than 300° C. and not more than 500° C., and is held in the temperature range for a tempering time of 20 seconds or more and 900 seconds or less, and during the reheating process, a carbide control parameter CP represented by the following formula (1) is set to 10,000 or more and 15,000 or less, Or further satisfying one or more of the following (a), (b) and (c): Area ratio of bainitic ferrite: 3.0% or more and 20.0% or less, Area ratio of tempered martensite: 40.0% or more and 90.0% or less, Area ratio of retained austenite: 3.8% or more and 15.0% or less, Carbon concentration in retained austenite: 0.60 mass% or more and 1.30 mass% or less, Area ratio of fresh martensite: 10.0% or less, Density of carbides in tempered martensite: 8.0 pieces / μm 2 The steel has a steel structure in which a remaining structure other than bainitic ferrite, tempered martensite, retained austenite and fresh martensite is one or more selected from ferrite, lower bainite, pearlite and carbide, the area ratio of the remaining structure being 27.8% or less and the area ratio of the pearlite being 5.0% or less, The base steel sheet has a diffusible hydrogen content of 0.50 ppm by mass or less, Furthermore, when a V-VDA bending test is performed up to the maximum load point, the length of the crack is 400 μm or less in the L cross section, and further, in a region formed at a position up to 50 μm on each side of a start line extending from the outer bend apex of the VDA bend to a position 50 μm in the plate thickness direction, with respect to the average grain size of bainitic ferrite in the plate thickness direction, the ratio of the average grain size before processing to the average grain size after processing is 5.0 or less, A method for manufacturing a steel plate having a tensile strength of 1180 MPa or more. CP=(T+273)×(k+1.2×logt)...Formula (1) where T is the tempering temperature (° C.), k is a material constant dependent on the C content, and t is the tempering time (seconds). k = -6 x C M +17.8, C M is the carbon content (mass%) in the martensite formed in the second cooling step. (a) A cold rolling step is included in which the steel sheet after the pickling step and before the annealing step is cold rolled to obtain a cold-rolled steel sheet. (b) a galvanizing step of subjecting the steel sheet after the first cooling step and before the second cooling step to a galvanizing treatment to form a galvanized layer on the steel sheet. (c) A metal plating step is included, which is performed after the pickling step and before the annealing step, of applying metal plating to one or both sides of the steel sheet to form a metal plating layer.

5. The method for producing a steel sheet according to claim 4, wherein the annealing in the annealing step is performed in an atmosphere with a dew point of −30° C. or higher.

6. A method for manufacturing a component, comprising the step of subjecting the steel plate according to claim 1 or 2 to at least one of forming and joining to form a component.

Citation Information

Patent Citations

  • Rust preventive painting method of automotive body

    JP1984053693A

  • Reeling method for thread

    JP1985052472A

  • High-strength steel sheet, high-strength hot-dip galvanized steel sheet, and high-strength hot-dip galvannealed steel sheet with excellent stretch flangeability and collision resistance, and method for producing the same

    JP3887235B2

  • High-strength steel sheet and method for manufacturing same

    WO2013051238A1

  • High-strength hot-dip zinc-coated steel sheet and method for manufacturing same

    WO2020136990A1